Prunin attenuates aflatoxin B1-induced testicular toxicity by alleviating oxidative stress and modulating TLR4/MyD88/NF-κB and Bax/Bcl-2/Caspase-3 signaling pathways - Muhammad Umar Ijaz; Ghulam Mustafa; Muhammad Zaid Salar; Amjad Islam Aqib; Ghulam Hussain; Aisha Khatoon; Hamida Hamdi (Tissue and Cell, 2027)

Development and Physicochemical Characterization of a pH and Thermo-Responsive Fusidic Acid-Loaded Polymeric Nanogel against Skin Infections - Hassan Ali; Azizullah Mukhtar; Umar Farooq; Shafi Ullah; Muhammad Tariq Khan; Tayyaba Zulfiqar; Izhar Ullah; Muhammad Farhan Ali Khan (Journal of Pharmaceutical Innovation, 2027)

Accuracy in prediction of reinforcement corrosion initiation: effects of time, chloride binding, and multidirectional exposures on concrete diffusivity - Shamsad Ahmad; Muhammad Umar Khan; Ashraf A. Bahraq; Mohammed A. Al-Osta; Amin Al-Fakih (European Journal of Environmental and Civil Engineering, 2026)

The role of exercise in MFN2 regulation in osteoarthritis - Jamal Alshorman; Ruba Altahla; Muhammad Umar (Molecular Biology Reports, 2026)

Epidemiological, clinical, and molecular studies on nail disorders in the human population of Punjab, Pakistan - Muhammad Tariq Shafi; Ali Umar; Muhammad Wajid (Molecular Biology Reports, 2026)

Enhanced decellularization of human amniotic membrane: optimizing dna clearance and protein retention for clinical applications - Damla Aykora; Gülfem Erbil; Özden Yülek; Fatma Beyazıt; Muhammad Umar Jajere; Cemre Aydeğer; Metehan Uzun (Molecular Biology Reports, 2026)

Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Experimental and numerical analysis of hybrid SMA-Steel wire mesh reinforced ECC for synergistic resilient infrastructure - Muhammad Umar; Peng Wang; Weiwen Li; Hui Qian; Zongao Li; Osama Zaid; Nabil Ben Kahla (Engineering Structures, 2026)

Phase-specific Fe0/H₂O₂ Fenton-like treatment enhances humification and suppresses antibiotic resistance gene rebound during sewage sludge composting - Imtiaz Ahmed; Dong Zhang; Muhammad Umar Farooq; Chengyu Li; Chenxuan Yu; Jiawang He; Zeshan Sheikh; Xiaohu Dai (Chemical Engineering Journal, 2026)

Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

Genomic characterization of genes controlling stay-green trait in bread wheat - Alia Anwar; Xingguo Ye; Hafiz Sabah-Ud-Din Mazhar; Muhammad Waleed Meeran; Ralf Müller-Xing; Muhammad Ashfaq; Muhammad Arshad Javed; Javaria Tabassum; Umar Masood Quraishi; Farheen Solangi; Shajiha Naeem (Euphytica, 2026)

Jarisch-Herxheimer reaction: A clinically neglected phenomenon in neurobrucellosis - Abdulbariu Ogirima Uhuami; Abdulrahman Adamu; Buhari Bawa; Abdurrahman Hassan Jibril; Muhammad Bashir Bello; Nafi’u Lawal; Mustapha Umar Imam (Next Research, 2026)

PANI/CeO₂ nanocomposite membranes for efficient simulated textile dye wastewater treatment: A data-driven approach - Amna Siddique; Hafiza Hifza Nawaz; Humaira Razzaq; Muhammad Umar; Shumaila Razzaque; Anila Tabasum; Xuqing Liu; Muhammad Wakil Shahzad (Journal of Environmental Chemical Engineering, 2026)

Disruptive shocks in global agri-food value chains: a comparative analysis of impact trajectories across 12 case studies - Muhammad Umar; Louise Manning; Conor Walsh (Global Environmental Change, 2026)

Sensors and smart food packaging for supply chains: Bridging expiration dates and actual perishability - Muhammad Umar Azam; Jolina Rodrigues; Mohamed Hamid Salim; Sarath Haridas Kaniyamparambil; Khalid Askar; Imane Belyamani; Blaise L. Tardy; Nouha Alcheikh (Food Control, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Antagonistic and synergistic interactions between Bacillus and Pseudomonas in the rhizosphere: Mechanistic basis, ecological constraints, and applications in plant growth promotion and disease suppression - Muhammad Mubeen; Bushra Mumtaz; Muhammad Umar Shafiq; Phyu Shin Thant; Tahir Mahmood; Muhammad Arslan Mushtaq; Sazada Siddiqui; Faisal Zulfiqar; Anam Moosa (Physiological and Molecular Plant Pathology, 2026)

Development of germinated chia seed flour fortified cupcakes - Mishal Malik; Muhammad Sibt-e-Abbas; Nahaa M. Alotaibi; Aisha Umar; Sabiha Abbas; Artur Banach; Sana Saadat; Soumya Ghosh (International Journal of Gastronomy and Food Science, 2026)

Redox-modulating metallic nanoparticles: mechanistic insights into pharmacological activity and cellular therapeutics - Muhammad Irfan; Umar Zeeshan; Haider; Ali Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Paternal lead exposure induces transgenerational oxidative stress and down-regulation of antioxidant genes in Drosophila melanogaster - Aminu Argungu Umar; Isah Musa Fakai; Mustapha Umar Imam; Abduljalil Muhammad Mode (Environmental Science and Pollution Research, 2026)

Melatonin and melatonin-functionalized quantum dots enhance antioxidant defense, attenuate cadmium uptake, and improve yield performance in bread wheat under cadmium stress - Shiza Mukhtar; Samina Bibi; Muhammad Anas; Munaza Mehreen; Umar Masood Quraishi (Biocatalysis and Agricultural Biotechnology, 2026)

Optimizing Nitrogen Fertilization through Combined Sources and Split Humic Acid Application Improves Wheat Productivity and Stress Resilience in Semi-arid Soils - Tahir Fazal; Muhammad Aurangzaib; Umar Arshad; Rashid Iqbal; Muhammad Raheel; Allah Ditta; Mohamed Taha Yassin (Water, Air, & Soil Pollution, 2026)

Helenalin: a multifaceted sesquiterpene lactone with diverse biological activities—an integrative pharmacological and computational evidence - Iqra Farzeen; Zunaira Jaan; Maryam Batool; Muhammad Muzammil Nazir; Derya Karatas Yeni; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Parental Iron Deficiency Programs Oxidative Stress and Epigenetic Demethylase Dysregulation (TET and KDM2) in Drosophila melanogaster Offspring - Farida Bashar; Kasimu Ghandi Ibrahim; Abdullahi Yahaya Abbas; Muhammad Bashir Bello; Mustapha Umar Imam; Aliu Abdulhameed Zubair (Biological Trace Element Research, 2026)

Transgenerational effects of maternal lead exposure on oxidative stress and antioxidant defense mechanisms in Drosophila melanogaster - Abduljalil Muhammad Mode; Isah Musa Fakai; Mustapha Umar Imam; Aminu Argungu Umar (Toxicology and Environmental Health Sciences, 2026)

Widespread Use of Banned Pesticides and Weak Regulatory Enforcement: Environmental and Health Implications Among Farmers in Gombe State, Nigeria - Mohammad Bashir Sulaiman; Babangida Hammani; Abdullahi Muhammad Gimba; Oluyinka Omoyeni Akinlotan; Aliyu Tijjani Fadawa; Umar Musa Kwami; Taibatu Idris Umar; Amina Muhammad Bello (Journal of Agromedicine, 2026)

Salicylic Acid and Proline-Functionalized Carbon Quantum Dots Mitigate Nickel Toxicity in Wheat by Enhancing Antioxidant Defense, Metal Homeostasis, and Nutritional Quality - Syed Abu Bakr Haider Bukhari; Minhas Elahi; Muhammad Anas; Shoaib Abbas; Waseem Ahmed Khattak; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Preclinical evaluation of silver-doped copper carbonate nanoparticles for antidiabetic and wound healing effects in mice - Muhammad Zahir Tahir; Ali Umar; Waseem Ul Ghafoor; Misbah Ullah Khan; Muhammad Saleem Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Reply to the comment on Zafar et al., 2025: “Retrieving petrogenetic source, compositional diversity and tectono-magmatic scenario of Tethyan sediment-derived magmatic flare-up: A tale from petrochemical and multi-isotopic (Sr–Nd–B–Hf) systematics” by Bhat, 2025 - Tehseen Zafar; Shuguang Song; Hafiz Ur Rehman; Hamed Gamaleldien; Abiola Oyebamiji; Zaheen Ullah; Umar Farooq Jadoon; Muhammad Farhan; Mohamed Zaki Khedr; Irfan Maqbool Bhat; Fatemeh Sepidbar; Fatemeh Nouri; et al. (Gondwana Research, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Lithology-driven machine and deep learning modelling for porosity prediction in shale reservoir systems using well logging data - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Muhammad Sajid; Manaf Muhammad; Abdul Wahid; Muhammad Ubaid Umar (Earth Science Informatics, 2026)

In-situ synthesis of ZIF-8@GO composites for efficient aqueous dye removal: a systematic study of performance and reusability - Khushboo Iman; Muhammad Umar Azam; Khalid Askar; Nouha Alcheikh; Rana Sabouni (Environmental Science and Pollution Research, 2026)

Assessing the impact of agricultural greenhouse gas emissions, financial development, and land use on cereal production in Sub-Saharan Africa: an econometric and machine learning approach - Abubakar Sabo Ahmad; Nazir Muhammad Abdullahi; Umar Shehu Umar; Bello Nasiru Abdullahi; Abdulaziz Nuhu Jibril; Amina Barau Inuwa; Mustapha Muhammad (Environment, Development and Sustainability, 2026)

Unlocking the Hydrocarbon Potential of the Canterbury Basin, New Zealand: Geochemical and Basin Modeling Insights for Hydrocarbon Exploration - Muhammad Ubaid Umar; Shenghe Wu; S. M. Talha Qadri; Shafqat Hussain; Khaled Albriki; Muhammad Riaz (Natural Resources Research, 2026)

Green-Synthesized Silver Nanoparticles Enhance Soybean Tolerance to Cadmium through Redox Regulation and Metabolic Reprogramming - Shifa Shaffique; Muhmmad Farooq; Muhmmad Saleem Khan; Ali Umar; Muhammad Aaqil Khan; Sang-Mo Kang; In-Jung Lee (Journal of Soil Science and Plant Nutrition, 2026)

Development and Optimization of a Fixed Dose Combination Tablet Containing Ibuprofen and Loratadine Using Design Expert and Box-Behnken Design - Muhammad Faheem; Lateef Ahmad; Umar Farooq; Kiramat Ali Shah; Ismail Khan; Abdur Rauf; Omar S. Bahattab; Yahya S. Al-Awthan; Anees Ahmed Khalil; Huda Ateeq (Journal of Pharmaceutical Innovation, 2026)

A review on the effects of iron (Fe) on Ulva prolifera: Mechanisms of growth promotion, inhibition, and biochemical responses - Md Mohidul Islam; Sahr Lamin Sumana; Mukhtar Abdullateef Muhammad; Gelena Urgesa Ayana; Shisi Fu; Abubakar Shuaibu; Ahmed E. Elshafey; Yifei Shen; Yuqing Sun; Md. Simul Bhuyan; Md. Enamul Hoq; Touhidul Hoque Shuvo; et al. (Algal Research, 2026)

Integrated modelling application for assessing impacts of climate and land use change on water balance in Hadejia river basin Northwestern Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Amir Kamal Hamidon; Ruhil Amal Adnan; Shaharin Ibrahim; Muhammad Amar bin Zaudi; AbdulJalal AbdulSalam (Arabian Journal of Geosciences, 2026)

Optimization and multivariate analysis of Schiff Base functionalized gold nanoparticle sensor for efficient bifenthrin detection in food samples - Syeda Bushra Anwar; Sana Yaqoob; Sufian Rasheed; Shujaat Ali; Abdul Rehman Umar; Kashif Hussain; Nazish Kousar; Kousar Yasmeen; Haji Muhammad; Abdul Hameed (Food Chemistry, 2026)

Cobalt nanostructures induced hematotoxicity and renal toxicity in albino mice: an experimental and computational evaluation - Ali Umar; Muhammad Saleem Khan; Muhammad Wajid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Correlation of tree stem diameter with root architecture, mechanical properties, and slope stability in a mountainous Cryptomeria plantation - Mehtab Alam; Jianfeng Chen; Usama Ayub; Umar Muhammad (Journal of Mountain Science, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

Numerical simulation of breakdown threshold voltage in charging coils of wireless power transfer systems - Umar Musa; Abdullahi Abubakar Mas’ud; Johnatan M. Rodríguez-Serna; Abdullahi Mohammad; Muhammad Lotfi Hussain; Firdaus Muhammad-Sukki (Next Research, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Comparative tissue level uptake of Lithium and Potassium across four urban tree species - Sahar AbdulHaq; Rida-Tuz- Zohra; Zafar Siddiq; Muhammad Umar Hayyat; Bushra Bilal (Trees, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Synergistic Effects of Polyethylene Microplastics and PGPR Pseudomonas fluorescens on Biochemical and Physiological Responses in Potato (Solanum tuberosum) - Masooma Batool; Laila Shahzad; Muhammad Umar Hayyat; Arifa Tahir (Potato Research, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Enhancing the immunogenicity of a recombinant PEDV subunit vaccine: the role of lipoprotein signal peptide - Haroon Afzal; Muhammad Umar; Nguyen-Thanh Hoa; Guan-Ming Ke; Li-Ting Cheng (Archives of Virology, 2026)

Retraction Note: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

Molecular characterization and genetic diversity of cotton whitefly Bemisia tabaci infesting cotton crops - Qamar Saeed; Muhammad Sagheer; Ummad ud din Umar; Muhammad Taimoor Shakeel; Mahmoud Moustafa; Mohammed Al-Shahrani; Uthman Algopishi; Muhammad Naeem; Mahmoud Ahmed Amer (International Journal of Tropical Insect Science, 2026)

Microplastics exacerbate antibiotic resistance by regulating microbial and functional gene dynamics in sludge and food waste composting - Imtiaz Ahmed; Dong Zhang; Muhammad Umar Farooq; Zeshan Sheikh; Xiaohu Dai (Water Research, 2026)

Microencapsulation of D-limonene through non-covalent coacervates of hemp protein isolate and gum Arabic - Muhammad Umar; Mohammad Fikry; Saeid Jafari; Kitipong Assatarakul (Journal of Food Engineering, 2026)

Sulfur–regolith composite material for radiation shielding on Mars: A sustainable ISRU approach - Muhammad Nazrif Zamani; Norhazilan Md Noor; Sarehati Umar; Mohamad Shazwan Ahmad Shah; Muhammad Syahir Sarkawi; Asyraf Arif Abu Bakar; Nur Hafizah A. Khalid; Hanis Hazirah Arifin (Journal of Cleaner Production, 2026)

Advancing seismic facies analysis and reservoir characterization: A synthetic data-augmented CNN and transfer learning workflow integrated with real seismic data - Muhammad Ali; Ning Wei; He Changxingyue; Keyao Lin; Wendong Wang; Muhsan Ehsan; Ren Jiang; Wakeel Hussain; Umar Ashraf (Gas Science and Engineering, 2026)

Laser-based quality assessment of stored apple: Integrating LIBS, LIPA, and DFT Analysis - Muhammad Umar Majeed; Asiri Iroshan; Muhammad Kashif Majeed; Hassnain Khalil; Huanqing Meng; Yuzhu Liu (Food Chemistry, 2026)

RETRACTED: Deepcluster: A selective and stable strategy to predict the AuPt-based high entropy alloy nanoclusters via deep reinforcement learning - Muhammad Usman; Muhammad Umar Farooq; Fuyi Chen (Chemical Engineering Journal, 2026)

Microencapsulation of Probiotics in Polymeric Microgels: Enhanced Viability and Stability through Inorganic Nanoparticle Doping - Muhammad Umar Farooq; Ashok Kumar Bishoyi; Nameer khairullah Mohammed; Suhas Ballal; Abhayveer Singh; Supriya S.; Faiyaz Ahmed; Laraib Shoukat; Noor Akram; Fakhar Islam (Probiotics and Antimicrobial Proteins, 2026)

Mitigating Chromium-Induced Toxicity in Wheat Using Quantum Dots: Physiological, Biochemical, and Seed Composition Responses in SKD-1 and Borlaug-16 Cultivars - Muhammad Anas; Amjid Khan; Umar Masood Quraishi (Journal of Soil Science and Plant Nutrition, 2026)

Undrained Strength and Deformation Behavior of Saturated Sand Under Large Strain Torsional Shear Tests - Muhammad Umar; Takashi Kiyota; Gabriele Chiaro (Geotechnical and Geological Engineering, 2026)

Radon concentration, its deterministic and probabilistic health risks through groundwater consumption, and spatial distribution - Said Muhammad; Fawad Hussain; Saeeda Yousaf; Zafar Iqbal; Umar Farooq; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Energy efficiency as a driver of climate resilience: global evidence - Muhammad Umar; Waqas Bin Khidmat (Energy Policy, 2026)

Long-term subsoiling and no-tillage with moderate nitrogen regulate soil carbon sequestration, microbial cbbL expression, and maize yield under semi-arid plastic mulching - Umar Daraz; Junhong Xie; Lingling Li; Yongjie Zhou; Muhammad Farhan Saeed; Aftab Jamal (Plant and Soil, 2026)

Synthesis of silver nanoparticles using vegetable waste, possible toxicities, and oxidative stress biomarker in Cyprinus carpio - Huma Ayub; Qaisar Khan; Umar Ijaz; Muhammad Asif Gondal; Raja Majid Khurshid (Fish Physiology and Biochemistry, 2026)

In silico characterization and molecular docking of the MIOX gene in Nile tilapia (Oreochromis niloticus) - Samra Farooq; Samra Shafqat; Jabbir Ali Khan; Ahmad Waheed; Ali Umar; Muhammad Saleem Khan (Fish Physiology and Biochemistry, 2026)

Deciphering auxin-regulated stomatal development: Novel insights into phytochrome-interacting factors, FOUR LIPS, and SNF1-related kinase interactions - Abdul Wakeel Umar; Naveed Ahmad; Hamad Hussain; Muhammad Zeeshan; Ming Xu (Plant Science, 2026)

Vernomigeodiins A–D, highly oxygenated stigmastane-type steroids isolated from Vernoniastrum migeodii with anti-herpes simplex virus activity - Morteza Yazdani; Anita Barta; Anasztázia Hetényi; Muhammad Bello Saidu; Umar Shehu Gallah; Róbert Berkecz; Antal Csámpai; Katalin Burián; Dóra Paróczai; Sara H.H. Ahmed; Judit Hohmann (Phytochemistry, 2026)

Communication-aware multi-agent reinforcement learning for cooperative navigation of multiple USVs in dynamic ocean environments - Umar Draz; Sana Yasin; Tariq Ali; Mohammad Hijji; Muhammad Ayaz; El-Hadi M . Aggoune (Ocean Engineering, 2026)

Ficus benjamina seed extract ameliorates high-sucrose-induced metabolic dysfunction by modulating insulin signalling and antioxidant pathways in drosophila - Muhammad Sani Ismaila; Diane Ignacio; Karla Georges; Kamaldeen Olalekan Sanusi; Mustapha Umar Imam; Kegan Romelle Jones; Venkatesan Sundaram (Next Research, 2026)

Ficus deltoidea Preserves Hippocampal Neuronal Integrity and Redox Balance in Oxidative Stress-Driven Alzheimer’s Disease-Like Rat Model - Alhaji Modu Bukar; Che Mohd Nasril Che Mohd Nassir; Michael Ayuba; Sushmita Devi Manoharan; Abdulhamid Sani Usman; Babagana Isa Umar; Zaw Myo Hein; Mohamad Aris Mohd Moklas; Muhammad Zulfadli Mehat; Hafizah Abdul Hamid (Molecular Neurobiology, 2026)

Molecular detection of helicobacter pylori amongst patients with peptic ulcer disease in Nigeria - Idayat Omotayo Oduola; Abubakar Basiru; Kabiru Mohammed; Asiya Umar; Abdulbariu Ogirima Uhuami; Lubabatu Ibrahim; Abdurrauf Auwal Muhammad; Kaisong Huang; Abdurrahman Hassan Jibril (Next Research, 2025)

Influence of superabsorbent polymer and jute covering as internal and external curing techniques on the concrete compressive strength development: Experimental and comparative computational analysis - Umar Khurram Iqbal Khan; Hilal Khan; Atif Mehmood Khan; Hassan Khan; Muhammad Jibran Tariq; Hashim Khan; Muhammad Aamir Khan (Next Research, 2025)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

Drosophila proteasome subunit Rpn8 controls IMD pathway activation via PGRP-SC2 degradation - Mingfei Wu; Umar Ali; Sen Ding; Chuchu Zhang; Yiheng Jin; Xinyan Cao; Muhammad Abdul Rehman Saeed; Yangyang Zhu; Muhammad Usama; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2025)

Investigating the Effect of Sn and Pt Doping and Co-doping on the Photocatalytic Efficiency of Zirconia for Degradation of Acid Yellow-76 - Mian Hussain Shah; Saima Sadiq; Umar Wahab; Inam Ullah; Sardar Hussain; Nasr Ullah; Safiullah Khan; Zaffar Iqbal; Muhammad Ismail; Aadil Nabi Chishti; Muhammad Sadiq (Water, Air, & Soil Pollution, 2025)

Modulating depression through the gut–brain axis: the role of gut microbiota in therapeutic interventions - Muhammad Muzammil Nazir; Warisha Ghaffar; Ghanva Mustafa; Saira Saeed; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Sofosbuvir containing ph-responsive hydrogel microparticulate system: design, characterization, and biocompatibility assessment - Muhammad Aun; Muhammad Umar Ashraf; Salim Albukhaty; Umaira Rehman; Asif Mahmood; Asma Razzaq; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Areej Alsubaie; Mounir M. Bekhit (Journal of Pharmaceutical Innovation, 2025)

Evaluating performances of SVR, HBA–SVR, and COOT–SVR techniques: monthly evaporation modeling in Algeria - Mohammed Achite; Muhammad Jehanzaib; Nehal Elshaboury; Muhammad Umar Khan; Kusum Pandey; Ehsan Mirzania (Euro-Mediterranean Journal for Environmental Integration, 2025)

R-CNN-TPOT: a new hybrid machine learning network for brain age prediction using EEG signal - Sundas Almas; Pedro Antonio Valdes Sosa; Rana Muhammad Ali Washakh; Rana Muhammad Umar Waque (Cognitive Neurodynamics, 2025)

Molecular detection and prevalence of colistin-resistant Escherichia coli in poultry and humans: a one health perspective - Muhammad Najam Ul Huda; Muhammad Zubair Shabbir; Adnan Hasan Tahir; Awais Ali Ahmad; Umar Bin Zahoor; Waqas Ahmad; Ali Raza; Farhan Afzal; Abdur Rauf Khalid; Muhammad Abu Bakr Shabbir (Brazilian Journal of Microbiology, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

Correction: Integrating digitalization, renewable energy, and institutional drivers in logistics sector: advancing sustainable economic growth in Asian economies - Wali Muhammad Khoso; Qingmei Tan; Rasool Bux Khoso; Muhammad Umar (Environment, Development and Sustainability, 2025)

Fluorescence spectroscopy as a tool for differentiating methicillin resistance in clinical isolates of Staphylococcus aureus - Rabia Anjum; Sana Imtiaz; Tahseen Rafaqat; Naeem Akhtar; Muhammad Saleem; Muhammad Umar (Journal of Fluorescence, 2025)

FinTech, environmental innovation, and social capital drive environmental and economic development in Asia - Yun Li; Muhammad Naeem Shahid; Muhammad Umar Islam; Muhammad Ishtiaq; Falak Sher (Environment, Development and Sustainability, 2025)

When farmers’ knowledge matters: Improving epidemiological understanding of Peste des petits ruminants in northern Nigeria - Zenaba MAHAMAT KODO; Usman Adamu RAYYANU; Mayowa Peter OLABODE; Victoria Isioma IFENDE; Rebecca Paul WEKA; Matthew Yakop GUKUT; Alexis DELABOUGLISE; Ismaila SHITTU; Yakubu Joel ATUMAN; Judith Dizot BAKAM; Falmata Haruna BWALA; Ladi Amos CHABIRI; et al. (Preventive Veterinary Medicine, 2025)

Heavy metals contamination of roadside dust, risk assessment, and their spatial distribution along the M-1 motorway - Sehrish Amin; Wajid Ali; Said Muhammad; Saeeda Yousaf; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Machine learning-driven porosity prediction: A case study from the Cretaceous Mata Series, Canterbury Basin, New Zealand - Muhammad Ubaid Umar; Shenghe Wu; S.M. Talha Qadri; Wakeel Hussain; Du Wei; Shaukat Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Water quality, risk assessment indices, and source apportionment across spatial patterns - Said Muhammad; Nizam Ullah; Wajid Ali; Sehrish Amin; Cem Tokatli; Imran Ud Din; Zafar Iqbal; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Recent advancements in UiO-66(Zr) MOFs and their derivatives: Designing water-stable membranes for water applications - Yahaya A. Muhammad; Muhammad Sajid; Abubakar Umar; Niaz Ali Khan; Ismail Abdulazeez; Billel Salhi; Nadeem Baig; Wail Falath (Desalination, 2025)

Comprehensive study on efficient diclofenac sodium removal using walnut and pistachio shell activated carbon: ANN, kinetics, isotherms, thermodynamics and DFT calculations - Sinem Temiz Seymen; Handan Atalay Eroğlu; Elif Nihan Kadıoğlu; Muhammad Umar; Ali Hamid; Hammad Khan; Sajjad Hussain; Feryal Akbal (Biomass and Bioenergy, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Climate change adjustment factor on rainfall depths in river basins of Khyber Pakhtunkhwa, Pakistan - Muhammad Umar (Climatic Change, 2025)

In silico identification of GTPase inhibitors from selected anti-gonorrheal plants against Neisseria gonorrhoeae - Blessing O. Awoyemi; Badmus Jamiu Damilare; Abdullahi Tunde Aborode; Che Muhammad Khairul Hisyam Ismail; Abdulqohar Adebayo; Haruna Isiyaku Umar; Ibrahim Akindeji Makinde; Ridwan Opeyemi Bello; Sodiq Fakorede; Mohammed M. Alshehri; Ahmed F. Alanazi (The Nucleus, 2025)

Selection criteria for the enhancement of nitrogen use efficiency in wheat using two step association analysis - Muhammad Amjad; Siddique Ahmad; Fahim Ullah Khan; Rafi Ullah; Iltaf Ullah; Muhammad Zahid Shah; Umar Bin Qasim (Vegetos, 2025)

Computer-aided design process of possible antisickling agents using molecular docking, pharmacokinetic assessment, homology modeling, and molecular dynamic studies targeting Hba protein - Stephen Ejeh; Habiba Asipita Otaru; Muhammad Tukur Ibrahim; Abdullahi Bello Umar; John Enyi Ejeh; Abduljelil Ajala; Samuel Ndaghiya Adawara; Ramith Ramu; Fabian Audu Ugbe; Joshua John; Idongesit Bassey Anweting (In Silico Pharmacology, 2025)

Meroterpenoids from Centrapalus pauciflorus leaves with antiproliferative activity - Muhammad Bello Saidu; Gordana Krstić; Anita Barta; Hazhmat Ali; István Zupkó; Umar Shehu Gallah; Dóra Rédei; Judit Hohmann (Phytochemistry Letters, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

Improving rheology and 3D printability of pea, fava and mung bean proteins with raw and fermented millet flour - Saphal Ghimire; Muhammad Umar; Chaiwut Gamonpilas; Anil Kumar Anal (Food Hydrocolloids, 2025)

Comparative Effects of Antibiotic and Antimicrobial Peptide on Growth Performance, Gut Morphology, Intestinal Lesion Score, Ileal Microbial Counts, and Immune Status in Broilers Challenged with Necrotic Enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Mubashar Ali; Muhammad Naveed Ul Haque; Muhammad Umar Zafar Khan; Sohail Ahmad (Probiotics and Antimicrobial Proteins, 2025)

Dose–response impact of arsenite on wheat (Triticum aestivum L.) genotypes: unravelling growth, accumulation, and antioxidant modulation for tolerance - Muhammad Saeed; Umar Masood Quraishi; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2025)

Isorhapontigenin: exploring a promising resveratrol analog for disease management through diverse signaling pathways—a review with computational insights - Muhammad Muzammil Nazir; Ghanva Mustafa; Saira Saeed; Warisha Ghaffar; Muhammad Umar Ijaz; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Integrating digitalization, renewable energy, and institutional drivers in logistics sector: advancing sustainable economic growth in Asian economies - Wali Muhammad Khoso; Qingmei Tan; Rasool Bux Khoso; Muhammad Umar (Environment, Development and Sustainability, 2025)

N-acetylcysteine as a feed additive to counteract ochratoxin A toxicity in poultry - Muntaha Tanveer; Muhammad Imran; Muhammad Kashif Saleemi; Mubashar Shareef; Muhammad Imran; Saqib Umar (Food Additives & Contaminants: Part A, 2025)

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Insect-based biofuels and animal feed additives: A sustainable energy and agricultural solution for Africa's future - Abdulbariu Ogirima Uhuami; Hadiza Aliyu; Badiat Jamila Danjumma; Saadatu Mohammed Bawa; Aminu Muhammad Lawal; Shamsudeen Umar Dandare; Aliyu Ibrahim Dabai (Next Research, 2025)

Effects of replacement of soybean meal with fermented soybean meal on growth performance, nutrient digestibility and carcass characteristics in broiler - Ali Husnain; Urooj Anwar; Asfa Fatima; Riaz Mustafa; Umar Farooq; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Aziz ur Rahman (Livestock Science, 2025)

Tailoring oxygen vacancy-rich 2D CoOOH/Alk-Ti₃C₂Tₓ MXene for enhanced persulfate activation and metronidazole degradation - Qurat Ul Ain; Muhammad Umar Farooq; M. Shameer Basha; Naseem Abbas (Journal of Water Process Engineering, 2025)

Role of Bacillus pseudomycoides in Enhancing the Nutritional Profile of Five Vigna radiata (L.) Cultivars Under Saline Stress - Bushra Bilal; Zafar Siddiq; Tehreema Iftikhar; Muhammad Umar Hayyat; Hammad Majeed (Journal of Soil Science and Plant Nutrition, 2025)

Enhanced you only look once v5s crack detection and classification technique by optimizing transformer architecture and convolutional complexity - Umar Ali; Muhammad Arshad Shehzad Hassan; Asim Khan; Muhammad Zeeshan Khan; Maryam Shahzadi (Innovative Infrastructure Solutions, 2025)

Prediction of compressive strength of stone dust-based fly ash bricks: experimental study and advanced machine learning algorithm - Mehtab Alam; Adil Khan; Muhammad Umar; Tauqir Ahmed; Ahmad Yar Mazari; Muhammad Usman Arshad (Innovative Infrastructure Solutions, 2025)

Geostatistical and multivariate analysis of phosphate evolution and its relationship with heavy metals in shallow groundwater in a Semi-Arid Basin - Saadu Umar Wali; Noraliani Binti Alias; Abdulqadir Abubakar Usman; Abdullahi Umar; Nasiru Muhammad; Ismail Usman Kaoje; Buhari Samaila; Basiru Aliyu; Habiba Muhammad Ladan; Mudassiru Atiku; Sa’ad Ibrahim (Earth Science Informatics, 2025)

Dispersal of Per- and polyfluoroalkyl substances (PFASs) and toxic metals: a probable influence of inorganic fluoride and ionic strength in the Shiqi River Basin of Nanjing City, South-Eastern China - Muhammad Ibrahim; Yiping Li; Xiaolin Zhu; Yaning Wang; Yan Chunmin; Hafsat Alhassan Danjaji; Abdulhakim Wagini Hassan; Adam Umar Jibo (Clean Technologies and Environmental Policy, 2025)

Cadmium and zinc inflows through wastewater irrigation govern soil metal balances in wheat-sorghum cropping system - Ayta Umar; Muhammad Nadeem; Shahid Hussain (Environmental Monitoring and Assessment, 2025)

Influence of décollement friction on magnetic fabrics of sedimentary rocks: Insights from AMS analysis in the Kohat fold-thrust belt, Pakistan - Muhammad Waqar Azeem; Baochun Huang; Umar Farooq Jadoon; Nazir Ur Rehman; Mohammad Metwaly; Muhammad Umar; Hongliang Lu; Yilian Liao (Journal of Asian Earth Sciences, 2025)

Antimony-doped NASICON-type solid electrolyte with homogeneous sodium-ion flux for high-temperature solid-state sodium batteries - Muhammad Akbar; Iqra Moeez; Ali Hussain Umar Bhatti; Young Hwan Kim; Mingony Kim; Ji-Young Kim; Jiwon Jeong; Jae Ho Park; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Review on crack detection in civil infrastructure using structural health monitoring and machine learning techniques - Muhammad Zeeshan Khan; Maryam Shahzadi; Asim Khan; Umar Ali; Muhammad Arshad Shehzad Hassan; Majid Hussain (Innovative Infrastructure Solutions, 2025)

Comment on: “Genome-wide association study of direct oral anticoagulants and their relation to bleeding” - Muhammad Umar Farooque Khoso; Muhammad Hammad Chola; Muhammad Hasan (European Journal of Clinical Pharmacology, 2025)

Evaluation of the shallow hydrothermal system in Jaboi Volcano based on the combination of remote sensing and geophysical measurements - Muhammad Yanis; Muhammad Isa; Nasrullah Zaini; Faisal Abdullah; Muksin Umar; Marwan; Cutti Zahrati; Bondan Galih Dewanto; Riski Ananda; Azman Abdul Ghani (Geosciences Journal, 2025)

High-Sensitivity RT-LAMP Assay Enables Rapid, Field-Deployable Detection of Candidatus Liberibacter Asiaticus in Crude DNA Extracts from Citrus Phyllosphere and Psyllid Vectors - Ummad ud Din Umar; Syed Muhammad Zaka; Muhammad Nauman Tahir; Muhammad Kashif; Ateeq Ur Rehman; Sagheer Atta; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Rapid synthesis of charged covalent organic framework for sustainable reverse osmosis membranes - Umar H. Nuhu; Niaz Ali Khan; Ijaz Hussain; Mengying Long; Billel Salhi; Nadeem Baig; Ismail Abdulazeez; Khan Alam; Sikandar Khan; Muhammad Usman; Umer Zahid; Isam H. Aljundi (Desalination, 2025)

A step towards rational design of hierarchical porous MOFs architectures for emerging practical implementations - Muhammad Umar Farooq; Rustem R. Zairov; Marsil K. Kadirov; Oleg G. Sinyashin; Bassim Arkook; Moussab Harb (Chemical Engineering Journal, 2025)

Promising Multi-Oxide Decorated Graphene Nanomaterials from Nickel Slag for Voltammetric Sensor Electrodes - Zul Arham; Muhammad Nurdin; Kurniawan Kurniawan; Ismaun Ismaun; Maulidiyah Maulidiyah; Akrajas Ali Umar; Sitti Jaria Ndora; Fika Ferlita (Water, Air, & Soil Pollution, 2025)

Preparation, Characterization and Removal of Acid Blue 129 and Erioglaucine Dyes from Aqueous Solution by Corn Cob Based Activated Carbon - Sultan Alam; Najeeb ur Rahman; Muhammad Ilyas; Iram --; AlSaba Gul; Muhammad Zahoor; Muhammad Naveed Umar; Riaz Ullah; Essam A. Ali (Bulletin of Environmental Contamination and Toxicology, 2025)

Virtual screening and molecular dynamic simulations of Desulfovibrio vulgaris dissimilatory sulfite reductase inhibitors for the control of sulphate reducing bacteria - Oluwafemi Adebayo Oyewole; Rahma Muhammad Adamu; Umar Saidu; Sekelwa Cosa; Mthokozisi B. C. Simelane; Md. Atiar Rahman; Mohammed Auwal Ibrahim (In Silico Pharmacology, 2025)

Advancing mangrove mapping with the integrated mangrove index (IMI) and the role of tidal dynamics - Muhammad Umar; Sawaid Abbas (International Journal of Remote Sensing, 2025)

Spatial distribution of hazard index via heavy metals consumption in water from the himalayan lacustrine ecosystems - Said Muhammad; Tauseef Ahmed; Sehrish Amin; Cem Tokatli; Fikret Ustaoğlu; Ashfaq Ahmad; Wajid Ali; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Green-fabricated MnO₂ nanoparticles function as dual nanofertilizers and chromium remediators, enhancing antioxidant pathways, ionomic networks, and physiological resilience in wheat - Muhammad Anas; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Restoring wheat productivity and nutrient balance under cadmium stress through reducing toxicity, metal uptake, and oxidative damage using selenium nanoparticles - Ayesha Jamil Abbasi; Muhammad Anas; Minhas Elahi; Amjid Khan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Shah Fahad; Hosam O. Elansary; Eman A. Mahmoud; Temoor Ahmed; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Long-term application of ozonation for removal of pharmaceuticals from wastewater treatment plant effluent: Effectiveness, control strategies, ecotoxicity - Tomáš Macsek; Pawel Krzeminski; Muhammad Umar; Taťána Halešová; Daniela Tomešová; Michal Novotný; Petr Hlavínek (Journal of Hazardous Materials, 2025)

Balancing well-being and environment: The moderating role of governance in sustainable development amid environmental degradation - Feng Wang; Seemab Gillani; Arshian Sharif; Muhammad Nouman Shafiq; Umar Farooq (Journal of Environmental Management, 2025)

Highly sensitive electrochemical sensing of fipronil using a ZnO/Graphene@C-dots hybrid nanocomposite - La Ode Agus Salim; Paulina Taba; Muhammad Zakir; Muhammad Nurdin; Abdul Wahid Wahab; Dahlang Tahir; St. Fauziah; Akrajas Ali Umar (Environmental Nanotechnology, Monitoring & Management, 2025)

Bergeyella zoohelcum: A first case report of its association with respiratory diseases in swine in China - Zenghai Jiang; Muhammad Umar Yaqoob; Abubakar Siddique; Juheng Guang; Abdelaziz Ed-Dra; Min Yue (Veterinary Research Communications, 2025)

Scrutinizing the role of two distinct elicitors modulating light harvesting potential, specific energy fluxes and physiological tolerance in maize plants under sub-optimal environment - Zamin Shaheed Siddiqui; Komal Nida; Muhammad Umar; Zainul Abideen; Khadija Irshad; Jean Wan Hong Yong (South African Journal of Botany, 2025)

Enhancing vegetation cover growth through water spreading bunds and dry afforestation in arid rangelands: Integrating remote sensing indicators with field insights - Sawaid Abbas; Aqeela Mobeen Akhter; Muhammad Mushtaque; Raja Muhammad Usama; Ansir Rasool; Muhammad Umar; Muhammad Uzair Mahmood; Marryam Malik (Science of The Total Environment, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Retrieving petrogenetic source, compositional diversity and tectono-magmatic scenario of Tethyan sediment-derived magmatic flare-up: A tale from petrochemical and multi-isotopic (Sr–Nd–B–Hf) systematics - Tehseen Zafar; Shuguang Song; Hafiz Ur Rehman; Hamed Gamaleldien; Abiola Oyebamiji; Zaheen Ullah; Umar Farooq Jadoon; Muhammad Farhan; Mohamed Zaki Khedr; Irfan Maqbool Bhat; Fatemeh Sepidbar; Fatemeh Nouri; et al. (Gondwana Research, 2025)

Identifying and prioritizing risks in urban rainwater harvesting projects: an ISM-MICMAC approach for sustainable water resources management - Ammara Ali; Sanna Ullah; Muhammad Asad Ali; Muhammad Umar Farooq; Wajih Ur Rehman; Mehdi Tlija (Stochastic Environmental Research and Risk Assessment, 2025)

Starvation from within: How heavy metals compete with essential nutrients, disrupt metabolism, and impair plant growth - Abdul Wakeel Umar; Muhammad Naeem; Hamad Hussain; Naveed Ahmad; Ming Xu (Plant Science, 2025)

Efficacy of ascorbic acid coated quantum dots in alleviating lead-induced oxidative damage and enhancing growth parameters in rice (Oryza sativa L.) for sustainable cultivation - Aliza Falak; Muhammad Anas; Amjid Khan; Alvina Hayat; Zeenat Shaheen; Muhammad Hamzah Saleem; Shah Fahad; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Mitigative effects of didymin against cadmium-induced renal injury via regulating Nrf-2/Keap-1, apoptosis, inflammation and oxidative stress - Ali Hamza; Sayda Snober Fatima Zadi; Muhammad Zaid Salar; Muhammad Umar Ijaz; Khalid A. Al-Ghanim; Ayesha Ishtiaq (Journal of Trace Elements in Medicine and Biology, 2025)

Production of 3D-printed meat analogues using pea, fava, and mung bean proteins: A comparison study - Saphal Ghimire; Chaiwut Gamonpilas; Muhammad Umar; Anil Kumar Anal (Food Structure, 2025)

Investigation of diabetes mellitus transmission in humans by using time delay tool and numerical treatment approach - Ali Raza; Ayesha Shabbir; Umar Shafique; Nauman Ahmed; Muhammad Rafiq (Modeling Earth Systems and Environment, 2025)

Thermal performance improvement of a solar distillation system using a spiral coil condenser with a parabolic dish - Muhammad Amin; Hamdani Umar; Teuku Azuar Rizal; Fazri Amir; Nasruddin A. Abdullah; Suma Fachruri Ginting; T.M. Indra Mahlia (Journal of Water Process Engineering, 2025)

Impacts of soiling on solar panel performance and state-of-the-art effective cleaning methods: A recent review - Nadia Shahzad; Naveed Hussain; Shayan Umar; Muhammad Farooq Azam; Tanzeela Yousaf; Adeel Waqas (Journal of Cleaner Production, 2025)

Seismic capacity assessment of eco-friendly fly ash brick masonry structures after retrofitting - Shah Zeb; Khan Shahzada; Umar Ahmad Noor; Muhammad Adeel Arshad; Abdur Rahim Khan; Haleem Ullah Khan (Innovative Infrastructure Solutions, 2025)

RETRACTED ARTICLE: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

Peptide-based vaccine design against Hendra virus through immunoinformatics approach - Asifa Sarfraz; Irfa Chaudhary; Fizza Arshad; Muhammad Shehroz; Asia Perveen; Umar Nishan; Abid Ali; Riaz Ullah; Abdelaaty A. Shahat; Aqal Zaman; Mohibullah Shah (Veterinary Immunology and Immunopathology, 2025)

In-silico evaluation of Cassia occidentalis phytochemicals for Plasmodium falciparum plasmepsin V inhibition: Revealing antimalarial potential - Aliyu Usman Maaji; Ramgopal Dhakar; Pankaj Kumar Teli; Umesh Garu; Umar Aliyu Adamu; Saminu Saminu Muhammad; Khalipha Ali Jubril; Fatima Idris Sambo (South African Journal of Botany, 2025)

Do structural and functional traits modulation determine the ecological fate of castor bean (Ricinus communis L.) under variable pedospheric and atmospheric conditions? - Ummar Iqbal; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (South African Journal of Botany, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Gold nanocatalysts supported on Mono-/Mixed oxides for efficient synthesis of methyl methacrylate - Muhammad Umar Farooq; Rustem R. Zairov; Bassim Arkook; Moussab Harb; Mohamed M Makhlouf (Fuel, 2025)

Smartphone-integrated inkjet-printed paper sensor and UV/Vis spectrophotometric method for on-site detection of As3+ and L-cysteine in food samples using novel AMTPP-functionalized silver nanoparticles - Sufian Rasheed; Kashif Hussain; Shan Arif; Abdul Rehman Umar; Syeda Bushra Anwar; Haji Muhammad; Kousar Yasmeen; Mustafa Tuzen; Muhammad Raza Shah (Food Chemistry, 2025)

Computer-aided rational design of a mRNA vaccine against Guanarito mammarenavirus - Mohibullah Shah; Asifa Sarfraz; Muhammad Shehroz; Asia Perveen; Samavia Jaan; Aqal Zaman; Umar Nishan; Arlindo A. Moura; Riaz Ullah; Zafar Iqbal; Mohamed A. Ibrahim (Biotechnology Letters, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

GIS-based spatial assessment of water quality, soil, and plant: a case study of Darawat Dam Sindh, Pakistan - Muhammad Farooque Lanjwani; Muhammad Yar Khuhawar; Rafi-O.-zaman Brohi; Waheed Ali Soomro; Abdul Hameed Lanjwani; Muhammad Umar Lanjwani (Environmental Monitoring and Assessment, 2025)

Impact of Indonesia's Forest Management Units on the reduction of forest loss and forest fires in Sulawesi - Colas Chervier; Stibniati S. Atmadja; Sandy Nofyanza; Choiriatun Nur Annisa; Fitri Nurfatriani; Rochadi Kristiningrum; Muhammad Alif K. Sahide; Ali Suhardiman; Syukur Umar (Ecological Economics, 2025)

Dendrite-free Sb-doped NASICON-type Na3Zr2Si2PO12 solid-electrolyte for stable solid-state sodium batteries - Muhammad Akbar; Mingony Kim; Iqra Moeez; Ali Hussain Umar Bhatti; Young Hwan Kim; Jiwon Jeong; Ji-Young Kim; Jae-Ho Park; Seungho Yu; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Development of Cellulose Acetate-Polyethylene Glycol-Chitosan Membrane-Embedded TiO2 Nanoparticles for Reverse Osmosis Desalination - Faizal Mustapa; Selvia Laki Wawe; La Ode Ahmad; Dwiprayogo Wibowo; Amir Mahmud; Maulidiyah Maulidiyah; Akrajas Ali Umar; Muhammad Nurdin (Water, Air, & Soil Pollution, 2025)

Particle size of wheat straw from genetically improved wheat affects the production performance and feeding behavior of Sahiwal cows - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Muhammad Qamar Bilal; Muhammad Riaz; Muhammad Farooq Khalid; Zia-Ur-Rehman; Urooj Anwar; Riaz Mustafa; Waseem Abbas; Umar Farooq (Tropical Animal Health and Production, 2025)

Retraction Note: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2024)

Reliable, Energy-Optimized, and Void-Aware (REOVA), Routing Protocol with Strategic Deployment in Mobile Underwater Acoustic Communications - Muhammad Umar Khan; Muhammad Aamir; Pablo Otero (Journal of Marine Science and Engineering, 2024)
The Underwater Acoustic Sensor Networks have gained significant attention because of their wide range of applications in submerged environments. However, ensuring reliable and energy-efficient communication in the submerged environment is challenging due to their distinctive characteristics such as limited energy resources, dynamic topology, extended propagation delays, and node mobility. Additionally, the void hole problem in submerged environments arises due to randomized node deployment. To curtail these issues, this paper introduces a novel way of strategically deploying the nodes based on the underwater depth parameters, which can reduce the likelihood of void hole occurrence. An optimal number of clusters based on the fixed transmission range of cluster heads is used to cater to extensive energy usage. In the proposed routing protocol, the path selection is based on the residual energy, link quality, and proximity to a higher number of nodes. Extensive simulations have been conducted by varying network parameters to analyze the network performance in terms of energy expenditure, packet delivery ratio, network throughput, number of dead nodes, and end-to-end delays. Also, the proposed work provides a performance comparison with some state-of-the-art protocols and exhibits promising results.

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Electronic, thermoelectric and magnetic properties of ternary telluride KAlTe2 and KInTe2 from theoretical perspective - Zahid Ullah; Muhammad Amir; Aiman Bazilla; Salim Ullah; Umar Shahzad; Nazir Ullah; Jabir Khan; Sabahat Gul (Next Research, 2024)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Structure-property relationship of ultrasound-assisted nanoemulsion-impregnated bioactive polysaccharide films for enhanced shelf life of mushrooms - Asif Ali Khan; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Mazhar Ul-Islam; Syed Asim Shah Bacha; Umar Zeb; Fang-Jie Yao; Sulaiman Ali Alharbi; Mansour Shrahili; Yan Yang; Wei Jia; et al. (Food Packaging and Shelf Life, 2024)

Combined toxicity of perfluoroalkyl substances and microplastics on the sentinel species Daphnia magna: Implications for freshwater ecosystems - Tayebeh Soltanighias; Abubakar Umar; Muhammad Abdullahi; Mohamed Abou-Elwafa Abdallah; Luisa Orsini (Environmental Pollution, 2024)

Taxifolin: A flavonoid in the freezing medium augments post-thaw semen quality and in vivo fertility potential of buffalo bull spermatozoa - Hussain Ahmed; Muhammad Umar Ijaz; Mehreen Riaz; Farhad Ullah; Haney Samir; Muhammad Shuaib; Ayman A. Swelum (Cryobiology, 2024)

Improving Short-term Daily Streamflow Forecasting Using an Autoencoder Based CNN-LSTM Model - Umar Muhammad Mustapha Kumshe; Zakariya Muhammad Abdulhamid; Baba Ahmad Mala; Tasiu Muazu; Abdullahi Uwaisu Muhammad; Ousmane Sangary; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Mosaad Ali Hussein Ali; Aliyu Uthman Bello; Muhammad Muhammad Bala (Water Resources Management, 2024)

Improving Irrigation Performance of Raised Bed Furrow Using WinSRFR Model - Muhammad Ayub Shah; Muhammad Waseem; Mudassar Iqbal; Ghulam Nabi; Muhammad Atiq Ur Rehman Tariq; Abu Bakar Arshed; Umar Sultan; Muhammad Laraib; Khawar Abbas (Water Conservation Science and Engineering, 2024)
Agricultural productivity is intricately tied to efficient water management strategies, with raised bed furrow systems being a prevalent method for irrigation. However, the optimization of these systems remains a critical area of exploration. The border irrigation method is commonly employed in developing countries for irrigation and leads to significant water loss, reduced irrigation efficiency, and increased irrigation durations. In contrast, raised bed furrow irrigation represents an improved surface irrigation technique that optimizes water usage in irrigated systems. This study seeks to assess the irrigation performance of raised bed furrows, encompassing deep percolation loss, distribution uniformity, adequacy, and application efficiency. The evaluation will be conducted for both existing conditions and an optimized scenario achieved through the application of the WinSRFR model. Field data facilitated the numerical simulation and the model was calibrated to reflect the existing irrigation system dynamics accurately. The performance of the model was assessed by utilizing the statistical indicator of root mean square error (RMSE) and revealed good agreement between advance and recession time. Results revealed that existing raised bed furrow irrigation exhibited up to 40% deep percolation loss, 80% distribution uniformity, and 60% application efficiency. Increasing furrow length had adverse effects; decreased application efficiency and distribution uniformity; and increased deep percolation losses. In contrast, reducing the furrow length and cutoff time by up to 33% and 40%, respectively, and increasing the width and inflow rate by up to 55% and 100%, respectively, enhanced the application efficiency and distribution uniformity, and minimized deep percolation loss. Overall, improved raised bed furrow irrigation provides a more efficient option and is encouraged to adopt for irrigation.

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

Nanoparticles in plant resistance against bacterial pathogens: current status and future prospects - Maria Gul; Raham Sher Khan; Zia Ul Islam; Sumayya Khan; Amina Shumaila; Sidra Umar; Sajad Khan; Brekhna; Muhammad Zahoor; Allah Ditta (Molecular Biology Reports, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Effectiveness of displacement compensation units for integral abutment bridges - Muhammad Umar Zulkefli; Pedro Ferreira (European Journal of Environmental and Civil Engineering, 2024)

Role of pressmud compost for reducing toxic metals availability and improving plant growth in polluted soil: Challenges and recommendations - Altaf Hussain Lahori; Maira Tunio; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Viola Vambol; Ambreen Afzal; Anila Kausar; Sergij Vambol; Aqsa Umar; Atif Muhammad (Science of The Total Environment, 2024)

Green recovery in BRICS economies: The role of mineral resources, energy productivity, and green innovation in sustainable development - Muhammad Umar; Nawazish Mirza; Zaghum Umar; Tatiana Sokolova (Resources Policy, 2024)

Integrated assessment of groundwater quality dynamics and Land use/land cover changes in rapidly urbanizing semi-arid region - Arif ullah; Sajjad Hussain; Yicheng Wang; Muhammad Awais; Meer Muhammad Sajjad; Nuaman Ejaz; Umar Javed; Muhammad Waqas; Xiao Zhe; Javed Iqbal (Environmental Research, 2024)

RNA interference: a promising biotechnological approach to combat plant pathogens, mechanism and future prospects - Amjad Ali; Muhammad Shahbaz; Fatih Ölmez; Noor Fatima; Ummad Ud Din Umar; Md. Arshad Ali; Muhammad Akram; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch (World Journal of Microbiology and Biotechnology, 2024)

Impact of Drought Duration and Severity on Drought Recovery Period for Different Land Cover Types in Balochistan, Pakistan - Hayat Ullah Khan; Muhammad Waseem; Mudassar Iqbal; Faraz Ul Haq; Abu Bakar Arshed; Muhammad Laraib; Umar Sultan (Journal of the Indian Society of Remote Sensing, 2024)

Site Response Analysis Considering Site-Affects Leading to Seismic Microzonation Map of Lahore - Maham Basharat; Ajwat Mustafa; Muhammad Umar; Mehtab Alam; Umair Ali; Muhammad Irfan (Geotechnical and Geological Engineering, 2024)

Adsorptive removal of cationic dyes from wastewater using a novel sodium alginate-based iron oxide nanocomposite hydrogel: DFT and advanced statistical physics modelling - Muhammad Umar; Muhammad Usman Farooq; Muhammad Arshad; Muhammad Usama; Feryal Akbal; Sajjad Hussain; Hammad Khan (Process Safety and Environmental Protection, 2024)

Surviving the desert's grasp: Decipherment phreatophyte Tamarix aphylla (L.) Karst. Adaptive strategies for arid resilience - Ummar Iqbal; Ali Daad; Ahmad Ali; Muhammad Faisal Gul; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq (Plant Science, 2024)

Dynamic performance of fiber-reinforced ultra-high toughness cementitious composites: A comprehensive review from materials to structural applications - Liangming Sun; Shuguang Liu; Hanbing Zhao; Umar Muhammad; Da Chen; Wengui Li (Engineering Structures, 2024)

Efficient reduction of antibiotic resistance genes and mobile genetic elements in organic waste composting via fenton-like treatment - Imtiaz Ahmed; Zixian Zhuang; Muhammad Umar Farooq; Hu Li; Shiquan Wang; Yanxia Zhong; Lizhi Zhang; Bo Zhang (Bioresource Technology, 2024)

Anatomical and Ionomics Investigation of Bread Wheat (Triticum aestivum L.) to Decipher Tolerance Mechanisms Under Arsenic Stress - Muhammad Anas; Muhammad Saeed; Kashif Naeem; Munib Ahmed Shafique; Umar Masood Quraishi (Journal of Plant Growth Regulation, 2024)

Synthesis of reduced graphene oxide supported FeCu and its environmental applications - Ayyaz Ahmad; Abdul Sattar Qureshi; Ali Hassan; Muhammad Arshad; Hifsa Khurshid; Umar Mehmood; Xuhong Guo (Environmental Science and Pollution Research, 2024)

Metabolites-induced co-evolutionary warfare between plants, viruses, and their associated vectors: So close yet so far away - Naveed Ahmad; Hamad Hussain; Muhammad Naeem; Saeed ur Rahman; Khalid Ali Khan; Babar Iqbal; Abdul Wakeel Umar (Plant Science, 2024)

A comprehensive investigation of the use of freeze concentration appro aches for the concentration of fish protein hydrolysates - Muhammad Umar Khan; Khalid Hamid; Ignat Tolstorebrov; Trygve M. Eikevik (Food Chemistry, 2024)

Azotobacter Modulate Nitrogen Assimilation, Sustain Light Harvesting Efficiency and Photosynthetic Performance of Maize Cultivar in a Saline Soil - Komal Nida; Zamin Shaheed Siddiqui; Manzer H. Siddiqui; Zeeshan Ahmed Salman; Muhammad Umar (Journal of Soil Science and Plant Nutrition, 2024)

Predicting Standard Penetration Test N-value from Cone Penetration Test Data Using Gene Expression Programming - Mehtab Alam; Jianfeng Chen; Muhammad Umar; Faheem Ullah; Muhammad Shahkar (Geotechnical and Geological Engineering, 2024)

Correction: Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Advancing nuclear science education through IRL Integration: A case experiment on criticality mass determination at the Kartini research reactor - Muhammad Zubair; Polina Matesha; Yumna Akram; Prasetyo Haryo Sadewo; Umar Sahiful Hidayat; Argo Satrio Wicaksono; Tri Nugroho Hadi Susanto (Annals of Nuclear Energy, 2024)

Neurotoxic snakebites in Africa: Clinical implications, therapeutic strategies, and antivenom efficacy - Abdulbaki Alfa-Ibrahim Adio; Ibrahim Malami; Nafiu Lawal; Amina Yusuf Jega; Bilyaminu Abubakar; Muhammad Bashir Bello; Kasimu Ghandi Ibrahim; Murtala Bello Abubakar; Abdussamad Abdussamad; Mustapha Umar Imam (Toxicon, 2024)

An ensemble-based strategy for robust predictive volcanic rock typing efficiency on a global-scale: A novel workflow driven by big data analytics - Umar Ashraf; Hucai Zhang; Aqsa Anees; Muhammad Ali; Hassan Nasir Mangi; Xiaonan Zhang (Science of The Total Environment, 2024)

A Robust Strategy of Geophysical Logging for Predicting Payable Lithofacies to Forecast Sweet Spots Using Digital Intelligence Paradigms in a Heterogeneous Gas Field - Umar Ashraf; Hucai Zhang; Hung Vo Thanh; Aqsa Anees; Muhammad Ali; Zhenhua Duan; Hassan Nasir Mangi; Xiaonan Zhang (Natural Resources Research, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Pore-scale simulation of flow in porous rocks for wall shear stress analysis - Yusron Feriadi; Muhammad Rizqie Arbie; Umar Fauzi; Fariduzzaman (Modeling Earth Systems and Environment, 2024)

Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

The feasibility of in-situ resource utilisation binder systems for construction materials on Mars: A review - Muhammad Nazrif Zamani; Mohamad Shazwan Ahmad Shah; Sarehati Umar; Nordin Yahaya; Nurul ‘Azizah Mukhlas; Jang Ho-Jay Kim; Norhazilan Md Noor (Advances in Space Research, 2024)

Optimizing Micronutrient Supplementation in Mango Orchards for the Suppression of Mango Anthracnose (Colletotrichum gloeosporioides) - Wajid Nazir; Syed Atif Hasan Naqvi; Niaz Ahmed; Ateeq ur Rehman; Abdulwahed Fahad Alrefaei; Muhammad Asif Zulfiqar; Ummad ud Din Umar (Applied Fruit Science, 2024)

Glycolipids biosurfactants production using low-cost substrates for environmental remediation: progress, challenges, and future prospects - Muhammad Aqif; Mansoor Ul Hassan Shah; Rawaiz Khan; Muhammad Umar; SajjadHaider; Saiful Izwan Abd Razak; Mat Uzir Wahit; Salah Ud-Din Khan; Magaret Sivapragasam; Shafi Ullah; Rab Nawaz (Environmental Science and Pollution Research, 2024)

Insight into mechanism of excellent visible-light photocatalytic activity of CuO/MgO/ZnO nanocomposite for advanced solution of environmental remediation - Muhammad Imran; Mohsin Raza; Hadia Noor; Sadia Muniza Faraz; Ali Raza; Umar Farooq; Mohammad Ehtisham Khan; Syed Kashif Ali; Omer Y. Bakather; Wahid Ali; Abdullateef H. Bashiri; Waleed Zakri (Chemosphere, 2024)

Ameliorative potential of eriocitrin against cadmium instigated hepatotoxicity in rats via regulating Nrf2/keap1 pathway - Muhammad Faisal Hayat; Muhammad Zohaib; Muhammad Umar Ijaz; Moazama Batool; Asma Ashraf; Bader O. Almutairi; Usman Atique (Journal of Trace Elements in Medicine and Biology, 2024)

Impact of urbanization on urban heat island intensity-a case study of Larkana City, Sindh, Pakistan - Muhammad Umar Lanjwani; Muhammad Farooque Lanjwani; Muhammad Hussain; Khalida Sodhar (Theoretical and Applied Climatology, 2024)

Exploiting and Enhancing the Heat Transport Rate of MoS2-Ag/EO Hybrid Nanofluid Flow via a Stretching Cylinder using Extended Yamada–Ota and Xue Models - Nahid Fatima; Ali Basem; Umar Farooq; Muhammad Imran; Haihu Liu; Taseer Muhammad; Sobia Noreen; Hassan Waqas (Journal of Fluorescence, 2024)

Integrated computational modeling and in-silico validation of flavonoids-Alliuocide G and Alliuocide A as therapeutic agents for their multi-target potential: Combination of molecular docking, MM-GBSA, ADMET and DFT analysis - Nusrat Shafiq; Misha Arshad; Awais Ali; Fatima Rida; Mohamed Mohany; Uzma Arshad; Muhammad Umar; Marija Milošević (South African Journal of Botany, 2024)

Metabolomics profiling reveals the detoxification and tolerance behavior of two bread wheat (Triticum aestivum L.) varieties under arsenate stress - Muhammad Saeed; Umar Masood Quraishi; Ghazala Mustafa; Abida Farooqi; Maria Greger; Riffat Naseem Malik (Food Chemistry, 2024)

Cu-TiO2-Aluminosilicate Nanocomposite as Highly Efficient Photocatalyst for Sustainable Removal of Cefixime Antibiotic: Synthesis, Optimization, and Toxicity Evaluation - Muhammad Umar Farooq; Qurat-Ul-Ain; Muhammad Irfan Jalees; Mahnoor Abid; Mirza Nadeem Ahmad; Maira Kaleem; Asma Tufail Shah; Juan Joon Ching (Environmental Processes, 2024)

Multiple Transgenic Strategies Positively Regulate Cold-Induced Sweetening in Low Temperature Stored Potato Tubers - Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Shazia Shafique; Nusrat Jahan; Muhammad Umar Bhatti; Rida Khalid; Ayman Naeem; Qamar Abbas; Sobiya Shafique; Bushra Tabassum (Potato Research, 2024)

Fabrication of Biopolymeric nanoparticles of colostrum whey-caseinate, Characterization, and In vitro digestibility - Muhammad Umar; Uracha Rungsardthong Ruktanonchai; Davids Makararpong; Atikorn Panya; Anil Kumar Anal (Journal of Food Engineering, 2024)

Development of a robust method for Cd(II) ions analysis using CeO2- and CeO2-Cu-BTC-based electrochemical sensors - Sabah Haider; Maria Zaib; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa; Shabnam Shahida; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Fintech and aluminium: Strategic enablers of climate change mitigation and sustainable mineral policy - Fangying Liu; Chi Wei Su; Ran Tao; Meng Qin; Muhammad Umar (Resources Policy, 2024)

Mineral resources and intellectual capital: Asymmetrical impacts and sustainable development outcomes - Linna Hao; Qin Meng; Muhammad Umar; Chi Long (Resources Policy, 2024)

Mineral resource investments and mutual funds performance: A remedy for recovery in BRICS - Zhuo Chen; Nawazish Mirza; Muhammad Umar; Zeina Sawtari; Xin Xie (Resources Policy, 2024)

Integrating DFT and machine learning for the design and optimization of sodium alginate-based hydrogel adsorbents: Efficient removal of pollutants from wastewater - Muhammad Umar; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Hyeok Choi; Eder C. Lima (Environmental Research, 2024)

Engineering nanoparticles for cancer immunotherapy: Current achievements, key considerations and future perspectives - Muhammad Umar Farooq; Charles H. Lawrie; Nan-Nan Deng (Chemical Engineering Journal, 2024)

Spatiotemporal analyses of temperature and equivalent temperature and their relationship with crop health across Pakistan’s cropland - Muhammad Latif; Momel Zoon; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi; Rashed Mahmood; Muhammad Umar (Theoretical and Applied Climatology, 2024)

Correction: Protective effect of didymin against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced reproductive toxicity in male rats - Arfa Tahir; Muhammad Umar Ijaz; Huma Naz; Tayyaba Afsar; Ali Almajwal; Houda Amor; Suhail Razak (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Protective effect of didymin against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced reproductive toxicity in male rats - Arfa Tahir; Muhammad Umar Ijaz; Huma Naz; Tayyaba Afsar; Ali Almajwal; Houda Amor; Suhail Razak (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Hydrochemical, hydrogeological, and cancer health risk analysis of groundwater due to anthropogenic activities, Hasilpur, Pakistan - Muhammad Irfan Jalees; Muhammad Atiq; Muhammad Umar Farooq; Ghulam Hussain; Mehwish Anis; Qurat Ul Ain; Maira Kaleem; Ahmad Ibrahim (Environmental Monitoring and Assessment, 2024)

Mineral resource Optimization: The Nexus of sustainability, digital transformation, and green finance in OECD economies - Min Zhong; Muhammad Umar; Nawazish Mirza; Adnan Safi (Resources Policy, 2024)

Exploring the dynamic interaction between geopolitical risks and lithium prices: A time-varying analysis - Xiaojing Zhang; Hsu-Ling Chang; Chi-Wei Su; Meng Qin; Muhammad Umar (Resources Policy, 2024)

Comparative morpho-physiological traits, antioxidant defense and nutritional profiling under Cd stress of japonica-indica elite rice (Oryza sativa L.) cultivars - Alvina Hayat; Muhammad Anas; Zeenat Shaheen; Aliza Falak; Umar Masood Quraishi (Journal of Crop Science and Biotechnology, 2024)

Climate change and desertification syndrome: the interaction of drivers in the drylands of Nigeria and the possibility of reducing adverse changes - Abubakar Ahmed; Mohd Yusoff Ishak; Nura Khalil Umar; Aminu Sulaiman Zangina; Muhammad Nasir Imam (Arabian Journal of Geosciences, 2024)

Efficient synergistic degradation of Congo red and omeprazole in wastewater using rGO/Ag@ZnO nanocomposite - Nazish Kousar; Sufian Rasheed; Kousar Yasmeen; Abdul Rehman Umar; Mouna Hind Laiche; Mohsin Masood; Haji Muhammad; Muddasir Hanif (Journal of Water Process Engineering, 2024)

Sustainable electric discharge machining using alumina-mixed deionized water as dielectric: Process modelling by artificial neural networks underpinning net-zero from industry - Muhammad Sana; Muhammad Asad; Muhammad Umar Farooq; Saqib Anwar; Muhammad Talha (Journal of Cleaner Production, 2024)

Functionalized carbon 1D/2D nanomaterials for effective water desalination: Synthesis, applications and cost issues. An overview - Umar Noor; Muhammad Fayyaz Farid; Ammara Sharif; Amna Saleem; Zubair Nabi; Muhammad Furqan Mughal; Kiran Abbas; Toheed Ahmed (Desalination, 2024)

The nexus between green intellectual capital, blockchain technology, green manufacturing, and sustainable performance - Muhammad Umar; Arslan Ahmad; Robert Sroufe; Zikri Muhammad (Environmental Science and Pollution Research, 2024)

Environmental regulation and green innovation efficiency: a revisit of the porter hypothesis based on Chinese cities - Liang Xu; Yusen Luo; Chao Wu; Muhammad Umar; Hongbo Li; Sulaman Muhammad (Environment, Development and Sustainability, 2024)

Pharmacotherapeutic potential of ginkgetin against polystyrene microplastics–instigated testicular toxicity in rats: A biochemical, spermatological, and histopathological assessment - Ali Akbar; Muhammad Umar Ijaz (Environmental Science and Pollution Research, 2024)

Arsenic accumulation pattern in water-soil-rice systems: A study of tolerance mechanisms and associated health risks - Muhammad Saeed; Muhammad Anas; Umar Masood Quraishi; Riffat Naseem Malik (Science of The Total Environment, 2024)

First report on genotypic estimation of MRSA load in udder of nomadic sheep flocks affected with subclinical mastitis in Pakistan - Muhammad Jawad Sabir; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Muhammad Umar Javed; Farwa Anwaar (Research in Veterinary Science, 2024)

Amentoflavone mediated hepatoprotection to counteract paraquat instigated hepatotoxicity via modulating Nrf2/keap1 pathway: A biochemical, inflammatory, apoptotic and histopathological study - Muhammad Umar Ijaz; Naila Ghafoor; Muhammad Faisal Hayat; Bader O. Almutairi; Usman Atique (Pesticide Biochemistry and Physiology, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Reconstructing high-resolution groundwater level data using a hybrid random forest model to quantify distributed groundwater changes in the Indus Basin - Arfan Arshad; Ali Mirchi; Javier Vilcaez; Muhammad Umar Akbar; Kaveh Madani (Journal of Hydrology, 2024)

A review of paleomagnetic constraints on the India-Asia collision: Paradoxes and perspectives - Umar Farooq Jadoon; Qian Zhao; Baochun Huang; Zhiyu Yi; Muhammad Waqar Azeem; Hongliang Lu; Syed Anjum Shah (Earth-Science Reviews, 2024)

A comprehensive study on the synchronized outgoing longwave radiation and relative humidity anomalies related to global Mw ≥ 6.5 earthquakes - Munawar Shah; Muhammad Umar Draz; Tahir Saleem (Natural Hazards, 2024)

Spatial soil loss prediction impacted by long-term land use/land cover change: a case study of Swat District - Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Saira Batool; Muhammad Umar Farooq (Environmental Monitoring and Assessment, 2024)

Phenomic profiling to reveal tolerance mechanisms and regulation of ascorbate–glutathione cycle in wheat varieties (Triticum aestivum L.) under arsenic stress - Muhammad Saeed; Umar Masood Quraishi; Tommy Landberg; Maria Greger; Riffat Naseem Malik (Environmental Geochemistry and Health, 2024)

An assessment of bilateral debt swap financing indispensable for economic growth and environment sustainability: a policy implication for heavily indebted countries - Umar Suffian Ahmad; Sadia Safdar; Muhammad Azam (Environmental Science and Pollution Research, 2023)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Antioxidant, anti-inflammatory, and anti-apoptotic effects of genkwanin against aflatoxin B1-induced testicular toxicity - Muhammad Umar Ijaz; Ayesha Ishtiaq; Arfa Tahir; Mughees Aizaz Alvi; Azhar Rafique; Peng Wang; Guo-ping Zhu (Toxicology and Applied Pharmacology, 2023)

Can sustainable resource management overcome geopolitical risk? - Adnan Safi; Muhammad Haseeb; Madeeha Islam; Muhammad Umar (Resources Policy, 2023)

Unleashing the dye adsorption potential of polyaminoimide homopolymer: DFT, statistical physics, site energy and pore size distribution analyses - Nabeel Hussain; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Muhammad Umar; Fazal Wahab (Journal of Environmental Chemical Engineering, 2023)

Unraveling the defensive strategies of camel thorn Alhagi maurorum medik. For thriving in arid and semi-arid environments - Ummar Iqbal; Ahmad Ali; Ali Daad; Muhammad Usama Aslam; Fahad Ur Rehman; Umar Farooq; Muhammad Faisal Gul (Journal of Arid Environments, 2023)

CA/PEG/chitosan membrane incorporated with TiO2 nanoparticles for strengthening and permselectivity membrane for reverse osmosis desalination - Dwiprayogo Wibowo; Faizal Mustapa; S. Selviantori; Muhammad Idris; Amir Mahmud; Maulidiyah Maulidiyah; Muh. Zakir Muzakkar; Akrajas Ali Umar; Muhammad Nurdin (Environmental Nanotechnology, Monitoring & Management, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

An autoencoder-based stacked LSTM transfer learning model for EC forecasting - Abdullahi Uwaisu Muhammad; Hamza Djigal; Tasiu Muazu; Jibril Muhammad Adam; Abdoul Fatakhou Ba; Umar Sani Dabai; Sani Tijjani; Muhammad Sabo Yahaya; Aliyu Ashiru; Umar Muhammad Mustapha Kumshe; Saddam Aliyu; Faruwa Ajibola Richard (Earth Science Informatics, 2023)

Phyto- and bio-management of metal(loid)-contaminated soil by inoculating resistant bacteria: evaluating tolerance of treated rice plant and soil with its efficiency - Zainab Tahir; Muhammad Umar Hayyat; Qaiser Farid Khan; Faiza Sharif; Muhammad Farhan; Laila Shahzad; Gul Zareen Ghafoor (Environmental Science and Pollution Research, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Relaxin (a regulatory-peptide) enhances cryotolerance, fertility potential and plasma reproductive hormones of Nili Ravi buffalo (Bubalus bubalis) during low breeding season - Hussain Ahmed; Sarwat Jahan; Muhammad Umar Ijaz; Mehreen Riaz; Farhad Ullah (Research in Veterinary Science, 2023)

Can Finland serve as a model for other developed countries? Assessing the significance of energy efficiency, renewable energy, and country risk - YanWei Wang; Tomiwa Sunday Adebayo; Fengyi Ai; Abdul Quddus; Muhammad Umar; Zilola Shamansurova (Journal of Cleaner Production, 2023)

How environmental regulation imperatives introduce innovation in firm financing choice among selected asian economies - Bilal Haider Subhani; Shen Zunhuan; Naheed Nawazesh Roni; Umar Farooq; Muhammad Asif Khan (Journal of Cleaner Production, 2023)

Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal Sajjad; Kashif Rasool; Azhar Siddique; Khadeeja Abdul Jabbar; Shimaa S. El-Malaha; Muhammad Umar Sohail; Fares Almomani; M. Rami Alfarra (Environmental Pollution, 2023)

Heat-Induced Transcriptome and Genome-Wide Analysis of NHL Genes in Maize (Zea mays L.) Suggest a Role of ZmNHLs Under Heat Stress - Muhammad Shahbaz; Farrukh Azeem; Muhammad Umar Rafique; Hafiz Muhammad Shahzaib Siraj; Muhammad Rizwan (Journal of Plant Growth Regulation, 2023)

Survival tactics of an endangered species Withania coagulans (Stocks) Dunal to arid environments - Ummar Iqbal; Fahad Ur Rehman; Muhammad Usama Aslam; Muhammad Faisal Gul; Umar Farooq; Amina Ameer; Naila Asghar; Ansar Mehmood; Khawaja Shafique Ahmad (Environmental Monitoring and Assessment, 2023)

The role of technological innovation, economic policy uncertainty, and poverty reduction in attaining environmental sustainability agenda: contextual evidence from developing South and East Asian Economies - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian; Umar Nawaz Kayani (Environment, Development and Sustainability, 2023)

3D graphene-based material: Overview, perspective, advancement, energy storage, biomedical engineering and environmental applications a bibliometric analysis - Ehtisham Umar; Muhammad Ikram; Junaid Haider; Walid Nabgan; Muhammad Imran; Ghazanfar Nazir (Journal of Environmental Chemical Engineering, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Rhizosphere microbiome assembly mediated by consecutive monoculture triggers the replant disease of Rehmannia glutinosa - Qian Li; Sisi Cai; Yuan Fang; Muhammad Umar Khan; Bianhong Zhang; Xuzhong Duan; Shutong Fan; Cuihong Lu; Mingjie Li; Li Gu; Juanying Wang; Jun Xiong; et al. (Applied Soil Ecology, 2023)

A Recent Digitalization in Recycling Industry Attaining Ecological Sustainability: A Comprehensive Outlook and Future Trend - Syed Abdul Rehman Khan; Muhammad Umar; Zhang Yu; Muhammad Tanveer Nawaz (Environmental Science and Pollution Research, 2023)

Correction: Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efciency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

The dynamic association between public environmental demands, government environmental governance, and green technology innovation in China: evidence from panel VAR model - Na Zhang; Jinqian Deng; Fayyaz Ahmad; Muhammad Umar Draz; Nabila Abid (Environment, Development and Sustainability, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Towards sustainable resource management: The role of governance, natural resource rent and energy productivity - Fei-fei Chen; Qiu-Su Wang; Muhammad Umar; Liya Zheng (Resources Policy, 2023)

Can geopolitical risk stably predict crude oil prices? A multi-dimensional perspective - Xin Li; Muhammad Umar; Cun-Bin Zhu; Camelia Oprean-Stan (Resources Policy, 2023)

Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efficiency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Quantifying irrigation water demand and supply gap using remote sensing and GIS in Multan, Pakistan - Muhammad Haseeb; Hafiz Umar Farid; Zahid Mahmood Khan; Muhammad Naveed Anjum; Akhlaq Ahmad; Muhammad Mubeen (Environmental Monitoring and Assessment, 2023)

Groundwater quality risk assessment using hydro-chemical and geospatial analysis - Hafiz Umar Farid; Hafiz Usman Ayub; Zahid Mahmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Rana Muhammad Asif Kanwar; Muhammad Mubeen; Pervaiz Sakinder (Environment, Development and Sustainability, 2023)

Estimation of component-wise runoff contribution using temperature index approach, in a snow- and glacier-fed transboundary Shyok River catchment of the Upper Indus Basin - Muhammad Umar Farooq; Muhammad Ashiq Kharal; Wolfgang Bogacki; Muhammad Fraz Ismail; Asif Mehmood (Arabian Journal of Geosciences, 2023)

Attenuative effect of astilbin on polystyrene microplastics induced testicular damage: Biochemical, spermatological and histopathological-based evidences - Arooj Rizwan; Muhammad Umar Ijaz; Ali Hamza; Haseeb Anwar (Toxicology and Applied Pharmacology, 2023)

Climate change adaptation strategies for sustainable water management in the Indus basin of Pakistan - Muhammad Muzammil; Azlan Zahid; Umar Farooq; Naeem Saddique; Lutz Breuer (Science of The Total Environment, 2023)

Breaking down the complexity of sustainable development: A focus on resources, economic complexity, and innovation - Adnan Safi; Xin Wei; Eduard Montesinos Sansaloni; Muhammad Umar (Resources Policy, 2023)

A Novel Machine Learning Approach for Detecting Outliers, Rebuilding Well Logs, and Enhancing Reservoir Characterization - Muhammad Ali; Peimin Zhu; Ma Huolin; Heping Pan; Khizar Abbas; Umar Ashraf; Jar Ullah; Ren Jiang; Hao Zhang (Natural Resources Research, 2023)

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone - Zaheen Ullah; Huan Li; Asad Khan; Shah Faisal; Yildirim Dilek; Michael W. Förster; Muhammad Farhan; Umar Ashraf; Salman Ahmed Khattak; Gohar Rehman; Syed Asim Hussain (International Geology Review, 2023)

How China is mitigating resource curse through infrastructural development? - Xiangfeng Ji; Tianyu Song; Muhammad Umar; Adnan Safi (Resources Policy, 2023)

Sulforaphane inclusion in a freezing medium augments post-thaw motility, functional and biochemical features, and fertility potential of buffalo (Bubalus bubalis) spermatozoa - Hussain Ahmed; Muhammad Umar Ijaz; Mehreen Riaz; Sarwat Jahan (Research in Veterinary Science, 2023)

The role of green finance in mitigating environmental degradation: Empirical evidence and policy implications from complex economies - Umar Numan; Benjiang Ma; Muhammad Sadiq; Hayat Dino Bedru; Can Jiang (Journal of Cleaner Production, 2023)

Transgenic maize inbred lines expressing high levels of Bacillus thuringiensis vegetative insecticidal protein (Vip3Aa86) offer effective control of maize stem borer (Chilo partellus) - Muhammad Umar Bhatti; Bushra Tabassum; Colin Berry; Anwar Khan; Uzma Qaisar; Ejaz Ali; Rida Khalid; Abdul Munim Farooq; Muhammad Tariq; Hasan Ayaz (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Testing the asymmetric effect of financial stability towards carbon neutrality target: The case of Iceland and global comparison - Chi-Wei Su; Muhammad Umar; Dervis Kirikkaleli; Abraham Ayobamiji Awosusi; Mehmet Altuntaş (Gondwana Research, 2023)

Therapeutic effect of gossypetin against paraquat-induced testicular damage in male rats: a histological and biochemical study - Shama Mustafa; Haseeb Anwar; Qurat ul Ain; Hussain Ahmed; Shabnoor Iqbal; Muhammad Umar Ijaz (Environmental Science and Pollution Research, 2023)

Mediation of gaseous emissions and improving plant productivity by DCD and DMPP nitrification inhibitors: Meta-analysis of last three decades - Muhammad Aammar Tufail; Muhammad Irfan; Wajid Umar; Abdul Wakeel; Ruth A. Schmitz (Environmental Science and Pollution Research, 2023)
Nitrification inhibitors (NIs), especially dicyandiamide (DCD) and 3,4-dimethylpyrazole phosphate (DMPP), have been extensively investigated to mitigate nitrogen (N) losses from the soil and thus improve crop productivity by enhancing N use efficiency. However, to provide crop and soil-specific guidelines about using these NIs, a quantitative assessment of their efficacy in mitigating gaseous emissions, worth for nitrate leaching, and improving crop productivity under different crops and soils is yet required. Therefore, based upon 146 peer-reviewed research studies, we conducted a meta-analysis to quantify the effect of DCD and DMPP on gaseous emissions, nitrate leaching, soil inorganic N, and crop productivity under different variates. The efficacy of the NIs in reducing the emissions of CO 2 , CH 4 , NO, and N 2 O highly depends on the crop, soil, and experiment types. The comparative efficacy of DCD in reducing N 2 O emission was higher than the DMPP under maize, grasses, and fallow soils in both organic and chemical fertilizer amended soils. The use of DCD was linked to increased NH 3 emission in vegetables, rice, and grasses. Depending upon the crop, soil, and fertilizer type, both the NIs decreased nitrate leaching from soils; however, DMPP was more effective. Nevertheless, the effect of DCD on crop productivity indicators, including N uptake, N use efficiency, and biomass/yield was higher than DMPP due to certain factors. Moreover, among soils, crops, and fertilizer types, the response by plant productivity indicators to the application of NIs ranged between 35 and 43%. Overall, the finding of this meta-analysis strongly suggests the use of DCD and DMPP while considering the crop, fertilizer, and soil types. Graphical Abstract

Asymmetric nexus between Bitcoin, gold resources and stock market returns: Novel findings from quantile estimates - Zhenzhen Jia; Sunil Tiwari; Jianhua Zhou; Muhammad Umar Farooq; Zeeshan Fareed (Resources Policy, 2023)

Tea pruning for the umbrella-shaped canopy can alleviate rhizosphere soil degradation and improve the ecosystem functioning of tea orchards - Yuhang Jiang; Xiaoqin Lin; Muhammad Umar Khan; Wenjia Jiang; Yina Xu; Zhong Li; Wenxiong Lin (CATENA, 2023)

Critical insight into sediment microbial fuel cell: Fundamentals, challenges, and perspectives as a barrier to black-odor water formation - Umar Abdulbaki Danhassan; Hongjian Lin; Ibrahim Lawan; Xin Zhang; Mahmoud H. Ali; Aliyu Idris Muhammad; Kuichuan Sheng (Journal of Environmental Chemical Engineering, 2023)

An integrated investigation of hydrocarbon pollution in Ahoada area, Niger Delta Region, Nigeria - Hafiz Aminu Umar; Mohd Faisal Abdul Khanan; Mohammed Sanusi Shiru; Anuar Ahmad; Muhammad Zulkarnain Abdul Rahman; Ami Hassan Md din (Environmental Science and Pollution Research, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Defects passivation by solution-processed titanium doping strategy towards high efficiency kesterite solar cells - Umar Farooq; Usman Ali Shah; Muhammad Ishaq; Ju-Guang Hu; Shehzad Ahmed; Shuo Chen; Zhuang-Hao Zheng; Zheng-Hua Su; Ping Fan; Guang-Xing Liang (Chemical Engineering Journal, 2023)

Impact of tourism development upon environmental sustainability: a suggested framework for sustainable ecotourism - Qadar Bakhsh Baloch; Syed Naseeb Shah; Nadeem Iqbal; Muhammad Sheeraz; Muhammad Asadullah; Sourath Mahar; Asia Umar Khan (Environmental Science and Pollution Research, 2023)

New trends in immunocastration and its potential to improve animal welfare: a mini review - Sohail Ahmed; Xunping Jiang; Guiqiong Liu; Amber Sadiq; Umar Farooq; Teketay Wassie; Ali Haider Saleem; Muhammad Zubair (Tropical Animal Health and Production, 2022)

Identification and primary distribution of Citrus viroid V in citrus in Punjab, Pakistan - Amjad Ali; Ummad ud din Umar; Sohail Akhtar; Muhammad Taimoor Shakeel; Ateeq ur Rehman; Muhammad Nouman Tahir; Sagheer Atta; Mahmoud Moustafa; Fatih Ölmez; Rashida Parveen (Molecular Biology Reports, 2022)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Oil palm yield prediction across blocks from multi-source data using machine learning and deep learning - Yuhao Ang; Helmi Zulhaidi Mohd Shafri; Yang Ping Lee; Shahrul Azman Bakar; Haryati Abidin; Mohd Umar Ubaydah Mohd Junaidi; Shaiful Jahari Hashim; Nik Norasma Che’Ya; Mohd Roshdi Hassan; Hwee San Lim; Rosni Abdullah; Yusri Yusup; et al. (Earth Science Informatics, 2022)

Studying green financing with economic development in BRI countries perspective: does public–private investment matter? - Ning Zhang; Muhammad Umar Farooq; Xiaoxue Zhang (Environmental Science and Pollution Research, 2022)

First report of cucumber-infecting cucurbit chlorotic yellows virus (CCYV) associated with cucurbit yellows disease in Pakistan - Muhammad Nouman; Tahir Farooq; Rashida Parveen; Ummad ud-Din Umar; Muhammad Naveed Aslam; Mahmoud Moustafa; Muhammad Taimoor Shakeel (Journal of Plant Pathology, 2022)

Correction: Fazal et al. Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions. J. Mar. Sci. Eng. 2022, 10, 800 - Abdul Ghaffar Fazal; Muhammad Umar; Faisal Shah; Muhammad Armaghan Faisal Miraj; Hammad Tariq Janjuhah; George Kontakiotis; Abdul Khaliq Jan (Journal of Marine Science and Engineering, 2022)
In the original publication [...]

Waste management and green technology: future trends in circular economy leading towards environmental sustainability - Muhammad Tanveer; Syed Abdul Rehman Khan; Muhammad Umar; Zhang Yu; Muhammad Jawad Sajid; Ikram Ul Haq (Environmental Science and Pollution Research, 2022)

Does sectoral modernization promote CO2 emissions? Dynamic panel analysis of selected Asian countries - Nabila Amin; Huaming Song; Muhammad Umar Farrukh (Environmental Science and Pollution Research, 2022)

Flooding tolerance in plants: from physiological and molecular perspectives - Nasrullah; Shahid Ali; Muhammad Umar; Lifang Sun; Muhammad Naeem; Humaira Yasmin; Naeem Khan (Brazilian Journal of Botany, 2022)

A Comprehensive Review About Bioactive Peptides: Sources to Future Perspective - Muhammad Naeem; Muhammad Inamullah Malik; Talha Umar; Swaiba Ashraf; Adnan Ahmad (International Journal of Peptide Research and Therapeutics, 2022)

Economic policy uncertainty and environmental degradation: the moderating role of political stability - Umar Farooq; Seemab Gillani; Bilal Haider Subhani; Muhammad Nouman Shafiq (Environmental Science and Pollution Research, 2022)

Sub-acute toxicity study on hydromethanolic leaves extract of Combretum hypopilinum (Combretaceae) Diels in Wistar rats - Mubarak Hussaini Ahmad; Abdulkadir Umar Zezi; Sherifat Bola Anafi; Omar Yahya Alshargi; Mustapha Mohammed; Sagir Mustapha; Auwal Adam Bala; Surajuddeen Muhammad; Sa’adatu Muhammad Julde; Abubakar Sadiq Wada; Abubakar Ibrahim Jatau (Toxicological Research, 2022)

Assessment of Climate Change and Its Impacts on the Flows of a Subtropical River Basin in the Hindu-Kush Mountain, South Asia - Muhammad Naveed Anjum; Abdulnoor A. J. Ghanim; Hafiz Umar Farid; Muhammad Zaman; Usama Muhammad Niazi; Saif ur Rahman; Mabkhoot A. Alsaiari; Muhammad Irfan (Pure and Applied Geophysics, 2022)

Correction to: Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al‑Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al-Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Mathematical modeling of sustainable development goals of India agenda 2030: a Neutrosophic programming approach - Ahteshamul Haq; Umar Muhammad Modibbo; Aquil Ahmed; Irfan Ali (Environment, Development and Sustainability, 2022)

Pollution profile, ecological and health risk assessment of trace metals in soils of auto mechanic workshops at Gombe metropolis, Gombe State, Northeastern Nigeria - Mohammad Bashir Sulaiman; Aishatu Hussein Santuraki; Abdullahi Muhammad Gimba; Sulaiman Babayo Ali; Aishatu Umar Barambu (Arabian Journal of Geosciences, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Evaluation and selection strategy for green supply chain using interval-valued q-rung orthopair fuzzy combinative distance-based assessment - Syed Abdul Rehman Khan; Manoj Mathew; P. D. D. Dominic; Muhammad Umar (Environment, Development and Sustainability, 2022)

Performance evaluation and comparison of observed and reanalysis gridded precipitation datasets over Pakistan - Sayed Waseem Iqbal; Muhammad Latif; Rehan Ahmed; Shahzada Adnan; Muhammad Umar; Burhan Ahmad; Muhammad Azam; Jabir Hussain Syed (Theoretical and Applied Climatology, 2022)

Supramolecular solvent–based liquid phase extraction of antimony prior to spectrophotometric quantification - Mansoor Khan; Muhammad Jamshed; Amir Badhshah; Umar Nishan; Mustafa Soylak (Environmental Monitoring and Assessment, 2022)

Salt tolerance screening of a newly developed wheat variety (AZRC-DK-84) in saline environment using halophytic grass (Cenchrus penisettiformis) as a test model - Basit Ali; Muhammad Umar; Muhammad Azeem; Zaheer Uddin; Zamin Shaheed Siddiqui (Acta Physiologiae Plantarum, 2022)

Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions - Abdul Fazal; Muhammad Umar; Faisal Shah; Muhammad Miraj; Hammad Janjuhah; George Kontakiotis; Abdul Jan (Journal of Marine Science and Engineering, 2022)
The geochemical investigation of shales from the Early to Middle Cretaceous Chichali Formation in the Hazara Basin was conducted to determine the origin, tectonic setting and evolution, paleo-weathering conditions, and paleo-oceanographic reconstruction. The research included a comprehensive field survey, sample collection, and analysis of a variety of main, trace, and rare-earth elements using an X-ray fluorescence spectrometer (XRF). Bivariate plots and ternary diagrams were used to determine the provenance, tectonic setting, and paleo-weathering conditions that existed during the development of the Chichali Formation in the Hazara Basin. The values of Ba/Sc, Ba/Co, Th/Sc, Cr/Th, Cr/Zr, Th/Co, Th/Cr, Sc/Th, bivariate plots of Al2O3 vs. TiO2, TiO2 vs. Zr, TiO2 vs. Ni, Df1–Df2, Zr vs. Nb, and La/Sc vs. Th/Co, and ternary diagram of K2O–Fe2O3–Al2O3 were used to illustrate the passive continental margin setting of Chichali Formation shales. The detailed chemical analysis also provides an understanding of the marine geochemical cycle, which reflects the origin of these sediments. The average K2O/Al2O3 value is less than 0.4, indicating that the shale contains clay minerals. The Chichali Formation’s Chemical Index of Alteration (mean = 71) and Index of Compositional Variation (mean = 1.12) values show a modest degree of chemical weathering in the source locations. From an environmental standpoint, the Chichali Formation is richer in toxic elements such as Ba, Zn, Ni, Cr, and Cu, which may be damaging to agricultural soils and drinking water when present in excess. These metals are incorporated into the formation during the weathering process.

Prevalence, transmission and molecular characterization of Cotton leaf curl Multan virus infecting hollyhock plants in Pakistan - Hajra Azeem; Rashida Perveen; Muhammad Nouman Tahir; Ummad-ud-din Umar; Fatih Ölmez; Amjad Ali (Molecular Biology Reports, 2022)

Taurine modulates dynamics of oxidative defense, secondary metabolism, and nutrient relation to mitigate boron and chromium toxicity in Triticum aestivum L. plants - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Muhammad Iqbal; Muhammad Umar Farooq; Muhammad Hamzah Saleem; Shafaqat Ali (Environmental Science and Pollution Research, 2022)

Efficacy of stem cell secretome in the treatment of traumatic brain injury: A systematic review and meta-analysis of preclinical studies - Suleiman Alhaji Muhammad; Abdullahi Yahya Abbas; Mustapha Umar Imam; Yusuf Saidu; Lawal Suleiman Bilbis (Molecular Neurobiology, 2022)

Correction to: Chemical remediation and advanced oxidation process of polychlorinated biphenyls in contaminated soils: a review - Muhammad Zaffar Hashmi; Muhammad Kaleem; Umar Farooq; Xiaomei Su; Paromita Chakraborty; Shams Ur Rehman (Environmental Science and Pollution Research, 2022)

Chemical remediation and advanced oxidation process of polychlorinated biphenyls in contaminated soils: a review - Muhammad Zaffar Hashmi; Muhammad Kaleem; Umar Farooq; Xiaomei Su; Paromita Chakraborty; Shams Ur Rehman (Environmental Science and Pollution Research, 2022)

Determinants of renewable energy sources in Pakistan: An overview - Umar Suffian Ahmad; Muhammad Usman; Saddam Hussain; Atif Jahanger; Maira Abrar (Environmental Science and Pollution Research, 2022)

A modified approach to quantify aquifer vulnerability to pollution towards sustainable groundwater management in Irrigated Indus Basin - Muhammad Umar; Shahbaz Nasir Khan; Arfan Arshad; Rana Ammar Aslam; Hafiz Muhammad Safdar Khan; Haroon Rashid; Quoc Bao Pham; Abdul Nasir; Rabeea Noor; Khaled Mohamed Khedher; Duong Tran Anh (Environmental Science and Pollution Research, 2022)

Biodiversity and ecological interactions of earthworm species from Poonch division Pakistan - Muhammad Umar Khan; Saiqa Andleeb; Muhammad Fiaz Khan; Rozina Ghulam Mustafa (Tropical Ecology, 2022)

A road map for environmental sustainability and green economic development: an empirical study - Syed Abdul Rehman Khan; Zhang Yu; Muhammad Umar (Environmental Science and Pollution Research, 2022)

Investigation of landslides with natural lineaments derived from integrated manual and automatic techniques applied on geospatial data - Simon Sadiq; Umar Muhammad; Michael Fuchs (Natural Hazards, 2022)

Remotely sensed image interpretation for assessment of land use land cover changes and settlement impact on allocated irrigation water in Multan, Pakistan - Maira Naeem; Hafiz Umar Farid; Muhammad Arbaz Madni; Rameez Ahsen; Zahid Mehmood Khan; Aqsa Dilshad; Huzaifa Shahzad (Environmental Monitoring and Assessment, 2022)

Enzymatic production of N-acetylneuraminic acid: advances and perspectives - Muhammad Iftikhar Hussain; Xiaolong Zhang; Xueqin Lv; Samra Basharat; Umar Shahbaz; Jianghua Li; Guocheng Du; Long Liu; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2022)

Nitrification Inhibitor and Plant Growth Regulators Improve Wheat Yield and Nitrogen Use Efficiency - Khadim Dawar; Umar Rahman; Syed Sartaj Alam; Mohammad Tariq; Aamir Khan; Shah Fahad; Rahul Datta; Subhan Danish; Shah Saud; Muhammad Noor (Journal of Plant Growth Regulation, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

The imperativeness of biomass energy consumption to the environmental sustainability of the United States revisited - Ayesha Bibi; Xibao Zhang; Muhammad Umar (Environmental and Ecological Statistics, 2021)

Facies Analysis and Sedimentary Architecture of Hybrid Event Beds in Submarine Lobes: Insights from the Crocker Fan, NW Borneo, Malaysia - Muhammad Jamil; Numair Ahmed Siddiqui; Nisar Ahmed; Muhammad Usman; Muhammad Umar; Hamad ur Rahim; Qazi Sohail Imran (Journal of Marine Science and Engineering, 2021)
Hybrid event beds represent the combined effect of multiple geological processes, which result in complex depositional geometries and distinct facies distribution in marine environments. Previous work on hybrid event beds highlights the classification, origin, and types of hybrid facies. However, in the present study, we discuss the development of hybrid event beds in submarine lobes with an emphasis on the analysis of proximal to distal, frontal to lateral relationships and evolution during lobe progradation. Detailed geological fieldwork was carried out in the classical deep-marine Late Paleogene Crocker Fan to understand the relationship between the character of hybrid bed facies and lobe architecture. The results indicate that hybrid facies of massive or structureless sandstone with mud clasts, clean to muddy sand, and chaotic muddy sand with oversized sand patch alternations (H1–H3) are well developed in proximal to medial lobes, while distal lobes mainly contain parallel to cross-laminated clean to muddy hybrid facies (H3–H5). Furthermore, lateral lobes have less vertical thickness of hybrid beds than frontal lobes. The development of hybrid beds takes place in the lower part of the thickening upward sequence of lobe progradation, while lobe retrogradation contains hybrid facies intervals in the upper part of stratigraphy. Hence, the development of hybrid beds in submarine lobe systems has a significant impact on the characterization of heterogeneities in deep-marine petroleum reservoirs at sub-seismic levels.

Investigating the myth of smokeless industry: environmental sustainability in the ASEAN countries and the role of service sector and renewable energy - Fayyaz Ahmad; Muhammad Umar Draz; Abbas Ali Chandio; Lijuan Su; Munir Ahmad; Muhammad Irfan (Environmental Science and Pollution Research, 2021)

Health risk assessment of endocrine disruptor bisphenol A leaching from plastic bottles of milk and soft drinks - Muhammad Umar Farooq; Muhammad Irfan Jalees; Qurat-ul-Ain; Ghulam Hussain; Mehwish Anis; Ummara Islam (Environmental Science and Pollution Research, 2021)

Investigating the flood damages in Lower Indus Basin since 2000: Spatiotemporal analyses of the major flood events - Salman Atif; Muhammad Umar; Fahim Ullah (Natural Hazards, 2021)

Sedimentary evolution of middle Jurassic epeiric carbonate ramp Hazara Basin Lesser Himalaya Pakistan - Malik Muhammad Saud Sajid Khan; Qasim Ali Jadoon; Muhammad Umar; Ahsan Ali Khan (Carbonates and Evaporites, 2021)

Effect of Pavement Thickness and Width on Liquefaction-Induced Settlements and the Contribution of Sand Ejecta in Total Settlement - Muhammad Mohsan; Takashi Kiyota; Muhammad Umar; Toshihiko Katagiri (Geotechnical and Geological Engineering, 2021)
This paper investigates the settlement in a pavement due to soil liquefaction. Four 1-g shaking table tests were performed on saturated sand bed-pavement model to understand the factors affecting the liquefaction-induced settlements and their relation to the pavement thickness and width. All the tests were performed with a base acceleration of 320 gal in a laminar box. The shaking table tests revealed that the total settlement reduced with the increase in the pavement thickness. The pavement with the same thickness but different width showed that the total settlement reduced with the increase in the pavement width. The co-seismic settlement and post-seismic settlement depend upon the thickness and width of the pavement, and the maximum contribution of the sand ejecta is around 7.7% in the total settlement.

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Factors affecting climate change concern in Pakistan: are there rural/urban differences? - Selim Jürgen Ergun; Muhammad Umar Khan; Maria Fernanda Rivas (Environmental Science and Pollution Research, 2021)

Environmental quality, climate indicators, and COVID-19 pandemic: insights from top 10 most affected states of the USA - Bilal; Muhammad Farhan Bashir; Khurram Shahzad; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan; Tehreem Fatima; Umar Numan (Environmental Science and Pollution Research, 2021)

Innovative initiative for effective operation and monitoring using HEC‐RAS modelling of Hakra Branch Canal System, Pakistan * - Muhammad Kamran; Wasif Yousaf; R.L.H.L. Rajapakse; Wakas Kareem Awan; Muhammad Riaz; Nayyar Minhaj Asif; Muhammad Umar; Usman Tehsin Shah (Irrigation and Drainage, 2021)
The Punjab Irrigation System is one of the world's largest contiguous systems, with its entire network extending over nearly 31,000 km in length. The system faces numerous constraints that limit the canal operations and their respective design discharges. Shortage of irrigation water is a contest that normally occurs at canal tail‐end users. The hydraulic performance of open canal networks is not easy to assess; therefore, it is impossible to feed the lateral offtakes with their design shares without changing designed or existing gate openings. To overcome these problems, a Hydrologic Engineering Center's River Analysis System (HEC‐RAS) model has been developed to simulate the flow situation in the canal system. For this study, the Hakra Branch Canal System with a command area of 1.4 million hectares was selected. To recognize model performance, water levels at the head of the canal and tail discharge have been compared with field data. The simulated results show the best‐fit match with field head water levels with coefficients of determination ( R 2 ) of 0.765 and 0.877 and tail discharges of the canal with R 2 = 0.707 and 0.945, for calibration and validation periods, respectively. The hydraulic simulation model is a useful tool for effective canal operation to determine the losses and find out the expected discharge for the tail‐end users. It has been observed that the proportion of excess actual delivery of water to lateral offtakes results in inadequate water supply for the tail‐end users. It is recommended that during the observation of the seasonally discharge table, the irrigation engineer should adjust a factor either in the HEC‐RAS model or in the observed data. It is also recommended to develop an unsteady model for considering sediment transport.

A Core Logging, Machine Learning and Geostatistical Modeling Interactive Approach for Subsurface Imaging of Lenticular Geobodies in a Clastic Depositional System, SE Pakistan - Umar Ashraf; Hucai Zhang; Aqsa Anees; Hassan Nasir Mangi; Muhammad Ali; Xiaonan Zhang; Muhammad Imraz; Saiq Shakeel Abbasi; Ayesha Abbas; Zaheen Ullah; Jar Ullah; Shucheng Tan (Natural Resources Research, 2021)

Multi-objective optimization modelling for analysing sustainable development goals of Nigeria: Agenda 2030 - Umar Muhammad Modibbo; Irfan Ali; Aquil Ahmed (Environment, Development and Sustainability, 2021)

RETRACTED ARTICLE: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2021)

The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Correction to: The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Delineating Novel Therapeutic Drug and Vaccine Targets for Staphylococcus cornubiensis NW1T Through Computational Analysis - Mohibullah Shah; Samavia Jaan; Batool Fatima; Muhammad Sameem Javed; Adnan Amjad; Asifullah Khan; Sahib Gul Afridi; Umar Nishan; Anwar Iqbal; Haq Nawaz (International Journal of Peptide Research and Therapeutics, 2021)

An integrated multi-objective optimization modelling for sustainable development goals of India - Irfan Ali; Umar Muhammad Modibbo; Jahangir Chauhan; Maryam Meraj (Environment, Development and Sustainability, 2021)

Hydrochemistry modelling: evaluation of groundwater quality deterioration due to anthropogenic activities in Lahore, Pakistan - Muhammad Irfan Jalees; Muhammad Umar Farooq; Mehwish Anis; Ghulam Hussain; Arfa Iqbal; Sana Saleem (Environment, Development and Sustainability, 2021)

Temporal Analysis for Detection of Anomalies in Precipitation Patterns over a Selected Area in the Indus Basin of Pakistan - Akhtar Ali; Hafiz Umar Farid; Zahid Mehmood Khan; Ijaz Ahmad; Muhammad Naveed Anjum; Muhammad Mubeen; Aamir Shakoor (Pure and Applied Geophysics, 2021)

Delineation of sinkhole in evaporite deposits using electrical resistivity survey: a case study of southern Kohat Plateau, Pakistan - Muhammad Waqar Azeem; Khaista Rehman; Nazeer Ur Rehman; Afrasiab; Umar Farooq; Adnan Arshad (Arabian Journal of Geosciences, 2021)

Synthetic β-hydroxy ketone derivative inhibits cholinesterases, rescues oxidative stress and ameliorates cognitive deficits in 5XFAD mice model of AD - Syed Ilyas Ahmad; Gowhar Ali; Tahir Muhammad; Rahim Ullah; Muhammad Naveed Umar; Aisha Nasir Hashmi (Molecular Biology Reports, 2020)

Effects of Replacing Inorganic with Respective Complexed Glycinate Minerals on Apparent Mineral Bioavailability and Deposition Rate in Tissues of Broiler Breeders - Wanjing Sun; Geng Wang; Xun Pei; Lujie Liu; Zhiping Xiao; Wenjing Tao; Muhammad Umar Yaqoob; Minqi Wang; Mingyan Huai; Lily Li; Wolf Pelletier (Biological Trace Element Research, 2020)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Retraction Note to: Impact of Drought Stress on Some Grain Quality Traits in Rice (Oryza sativa) - Zulqarnain Haider; Umar Farooq; Imad Naseem; Samta Zia; Muhammad Alamgeer (Agricultural Research, 2020)

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

Correction to: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Environmental pollution and COVID-19 outbreak: insights from Germany - Bilal; Muhammad Farhan Bashir; Maroua Benghoul; Umar Numan; Awais Shakoor; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan (Air Quality, Atmosphere & Health, 2020)

Does asymmetric persistence in convergence of the air quality index (AQI) exist in China? - Xue-Tao Zhang; Xi-Hua Liu; Chi-Wei Su; Muhammad Umar (Environmental Science and Pollution Research, 2020)

Application of regression in seasonal flow forecasting for Upper Indus Basin of Pakistan - Muhammad Umar (Arabian Journal of Geosciences, 2020)

Zinc Nutrition for Improving the Productivity and Grain Biofortification of Mungbean - Muhammad Umar Haider; Mubshar Hussain; Muhammad Farooq; Ahmad Nawaz (Journal of Soil Science and Plant Nutrition, 2020)

Microfacies, diagenesis and hydrocarbon potential of Eocene carbonate strata in Pakistan - Umer Khitab; Muhammad Umar; Muhammad Jamil (Carbonates and Evaporites, 2020)

Advances in exogenous RNA delivery techniques for RNAi-mediated pest control - Olawale Samuel Adeyinka; Saman Riaz; Nida Toufiq; Iqra Yousaf; Muhammad Umar Bhatti; Anicet Batcho; Amos Afolarin Olajide; Idrees Ahmad Nasir; Bushra Tabassum (Molecular Biology Reports, 2020)

RETRACTED ARTICLE: Environmental efficiency and the role of energy innovation in emissions reduction - Muhammad Khalid Anser; Wasim Iqbal; Umar Suffian Ahmad; Arooj Fatima; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Sodium arsenite toxicity on hematology indices and reproductive parameters in Teddy goat bucks and their amelioration with vitamin C - Muhammad Zubair; Maqbool Ahmad; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Mushtaq Ahmad; Christopher Joseph Martyniuk; Qudrat Ullah; Saqib Umar (Environmental Science and Pollution Research, 2020)

Resistance to Chilo infuscatellus (Lepidoptera: Pyraloidea) in transgenic lines of sugarcane expressing Bacillus thuringiensis derived Vip3A protein - Saman Riaz; Idrees Ahmad Nasir; Muhammad Umar Bhatti; Olawale Samuel Adeyinka; Nida Toufiq; Iqra Yousaf; Bushra Tabassum (Molecular Biology Reports, 2020)

Fabrication of Pt-Pd@ITO grown heterogeneous nanocatalyst as efficient remediator for toxic methyl parathion in aqueous media - Ali Muhammad Mahar; Aamna Balouch; Farah Naz Talpur; Abdullah; Pirah Panah; Raj Kumar; Ameet Kumar; Abdul Hameed Pato; Dadu Mal; Sagar Kumar; Akrajas Ali Umar (Environmental Science and Pollution Research, 2020)

TiO2 Coated-Asphalt Buton Photocatalyst for High-Performance Motor Vehicles Gas Emission Mitigation - Muhammad Zakir Muzakkar; Muhammad Nurdin; Ima Ismail; Maulidiyah Maulidiyah; Dwiprayogo Wibowo; Ratna Ratna; Siti Khatijah Md Saad; Akrajas Ali Umar (Emission Control Science and Technology, 2020)

Migration and Household Adaptation in Climate-Sensitive Hotspots in South Asia - Amina Maharjan; Ricardo Safra de Campos; Chandni Singh; Shouvik Das; Arjun Srinivas; Mohammad Rashed Alam Bhuiyan; Sultan Ishaq; Muhammad Awais Umar; Tanzina Dilshad; Krity Shrestha; Suruchi Bhadwal; Tuhin Ghosh; et al. (Current Climate Change Reports, 2020)
Purpose of Review South Asia is highly vulnerable to the impacts of climate change, owing to the high dependency on climate-sensitive livelihoods and recurrent extreme events. Consequently, an increasing number of households are adopting labour migration as a livelihood strategy to diversify incomes, spread risks, and meet aspirations. Under the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA) initiative, four research consortia have investigated migration patterns and their inherent linkages to adaptation to climate change in climate hotspots. This article synthesizes key findings in regional context of South Asia. Recent Findings The synthesis suggests that in climate-sensitive hotspots, migration is an important livelihood diversification strategy and a response to various risks, including climate change. Typically, one or more household members, often young men, migrated internally or internationally to work in predominantly informal sectors. Remittances helped spatially diversify household income, spread risks, and insure against external stressors. The outcomes of migration are often influenced by who moves, where to, and what capacities they possess. Summary Migration was found to help improve household adaptive capacity, albeit in a limited capacity. Migration was mainly used as a response to risk and uncertainty, but with potential to have positive adaptation co-benefits.

Photocatalytic degradation and kinetic modeling of azo dye using bimetallic photocatalysts: effect of synthesis and operational parameters - Nadia Riaz; Maryam Hassan; Maria Siddique; Qaisar Mahmood; Umar Farooq; Rizwana Sarwar; Muhammad Saqib Khan (Environmental Science and Pollution Research, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Spatiotemporal trends in reference evapotranspiration over South Korea - Ju Ha Hwang; Muhammad Azam; Maeng Seung Jin; Yong Ho Kang; Jae Eun Lee; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Muhammad Zaffar Hashmi (Paddy and Water Environment, 2020)

Photoperiodic stress induces genotype-specific shift in DNA methylation in Tartary buckwheat - Muhammad Saad; Helen Mary; Umar Amjid; Ghulam Shabir; Kashif Aslam; Shahid Masood Shah; Abdul Rehman Khan (Biologia Futura, 2019)
Tartary buckwheat, known for its rich source of health beneficial secondary metabolites, is cultivated in many areas of the world. Among different environmental factors, photoperiod strongly influence its growth, flowering time, and ultimately the yield. In this context, epigenetics could contribute significantly in the regulation of plant response against changing environment. Therefore, with the aim to study the involvement of DNA methylation in photoperiod mediated plant response, genome-wide DNA methylation analysis was performed in two accessions (A1 and A2) of Tartary buckwheat using three photoperiodic treatments, i.e., 10-hr light/day (T1), 12-hr light/day (T2), and 14-hr light/day (T3). Flowering time and plant fresh weight data revealed that accessions A1 and A2 prefer T1 and T2 treatments, respectively. Total DNA methylation ratio increased with the increase in photoperiod in accession A1 but decreased under same conditions in accession A2. Full methylation increased significantly while intensive decrease in hemimethylation was noted from T2 to T3 in A1, whereas full methylation strongly increased and hemimethylation strongly decreased from T1 to T2 in A2. Overall, the DNA methylation events appeared more frequently than demethylation events. This study reports for the first time an accession-/genotype specific pattern of shift in the DNA methylation under different photoperiodic treatments that will pave the way toward identification of specific genes involved in the regulation of plant response against photoperiodic stress.

Citric Acid Functionalized Bougainvillea spectabilis: a Novel, Sustainable, and Cost-effective Biosorbent for Removal of Heavy Metal (Pb2+) from Waste Water - Huma Nazir; Muhammad Salman; Makshoof Athar; Umar Farooq; Abdul Wahab; Momal Akram (Water, Air, & Soil Pollution, 2019)

An overview of climate change and variability impact studies in Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Ahmad Zaharin Aris; Wan Nor Azmin Sulaiman; Muhammad Amar Zaudi; Abubakar Ibrahim Tukur (Arabian Journal of Geosciences, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

Periodic vicissitudes of different concentrations of a developed prototype killed S. aureus mastitis vaccine on immune modulators, mediators and immunoglobulins in cows - Idris Umar Hambali; Faez Firdaus Jesse Bin Abdullah; K. R. Bhutto; M. L. Mohd Azmi; A. H. Wahid; Z. Zakaria; M. N. Odhah; M. Arsalan; N. A. Muhammad; M. N. Jefri (Tropical Animal Health and Production, 2019)

The impact of carbon emission and forest activities on health outcomes: empirical evidence from China - Muhammad Umar Farooq; Umer Shahzad; Suleman Sarwar; Li ZaiJun (Environmental Science and Pollution Research, 2019)

Geochemical attributes of late Neoproterozoic Salt Range Formation, Pakistan: constraints on provenance, paleoclimate, depositional and tectonic settings - Muhammad Ahmed Farooqui; Muhammad Umar; Muhammad Amjad Sabir; Rashid Pervez; Tarib Jalees (Geosciences Journal, 2019)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Potentially toxic elements in soil of the Khyber Pakhtunkhwa province and Tribal areas, Pakistan: evaluation for human and ecological risk assessment - Umar Saddique; Said Muhammad; Mohsin Tariq; Hua Zhang; Mohammad Arif; Ishtiaq A. K. Jadoon; Nimat Ullah Khattak (Environmental Geochemistry and Health, 2018)

Potential Toxic Metal Accumulation in Soil, Forage and Blood Plasma of Buffaloes Sampled from Jhang, Pakistan - Zafar Iqbal Khan; Ilker Ugulu; Sara Umar; Kafeel Ahmad; Naunain Mehmood; Asma Ashfaq; Humayun Bashir; Muhammad Sohail (Bulletin of Environmental Contamination and Toxicology, 2018)

Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Muhammad Yaqoob; Li Ping Wang; Jam Kashif; Javed Memon; Sajid Umar; Muhammad Farooq Iqbal; Muhammad Fiaz; Cheng-Ping Lu (Folia Microbiologica, 2018)

Potential harmful elements in coal dust and human health risk assessment near the mining areas in Cherat, Pakistan - Muhammad Ishtiaq; Noor Jehan; Said Akbar Khan; Said Muhammad; Umar Saddique; Bushra Iftikhar; Zahidullah (Environmental Science and Pollution Research, 2018)

The Potential Use of Vetiveria zizanioides for the Phytoremediation of Antimony, Arsenic and Their Co-Contamination - Nosheen Mirza; Hussani Mubarak; Li-Yuan Chai; Wang Yong; Muhammad Jamil Khan; Qudrat Ullah Khan; Muhammad Zaffar Hashmi; Umar Farooq; Rizwana Sarwar; Zhi-Hui Yang (Bulletin of Environmental Contamination and Toxicology, 2017)

Assessment of heavy metals concentration in phosphate rock deposits, Hazara basin, Lesser Himalaya Pakistan - Faridullah Faridullah; Muhammad Umar; Arif Alam; Muhammad Amjad Sabir; Danyal Khan (Geosciences Journal, 2017)

Diurnal thermoregulatory responses in pregnant Yankasa ewes to the dry season in a tropical Savannah - Lukuman Surakat Yaqub; Joseph Olusegun Ayo; Muhammad Umar Kawu; Peter Ibrahim Rekwot (Tropical Animal Health and Production, 2017)

Water-saving technologies affect the grain characteristics and recovery of fine-grain rice cultivars in semi-arid environment - Khawar Jabran; Muhammad Riaz; Mubshar Hussain; Wajid Nasim; Umar Zaman; Shah Fahad; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Impacts of changing climate and snow cover on the flow regime of Jhelum River, Western Himalayas - Muhammad Azmat; Umar Waqas Liaqat; Muhammad Uzair Qamar; Usman Khalid Awan (Regional Environmental Change, 2017)

Comparative study of performance of real-time satellite-derived rainfall in Swat Catchment - Muhammad Umar; Adil Latif; Syed Amer Mahmood (Arabian Journal of Geosciences, 2017)

Haematology and blood chemistry references values for clinically healthy red-wattled lapwing (Vanellus indicus) - Sajid Umar; Kiran Aqil; Rizwan Qayyum; Muhammad Younus; Qamar-un-Nisa; Shahzad Ali; Muhammad Ali Shah; Muhammad Irfan; Muhammad Usman; Asif Ali; Akbar Ali; Adnan Ayan; et al. (European Journal of Wildlife Research, 2016)

Comparative enzyme inhibition study of 1-deazapurines - Iftikhar Ali; Ajmal Khan; Amjad Hussain; Umar Farooq; Muhammad Ismail; Viqar Hyder; Viqar U. Ahmad; Viktor O. Iaroshenko; Hidayat Hussain; Peter Langer (Medicinal Chemistry Research, 2016)

Computing soil creep velocity using dendrochronology - Mohammad Amjad Sabir; Muhammad Umar; Muhammad Farooq; Faridullah Faridullah (Bulletin of Engineering Geology and the Environment, 2016)

Recent Climate Trends and Drought Behavioral Assessment Based on Precipitation and Temperature Data Series in the Songhua River Basin of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Shuhua Dong; Umar Waqas Liaqat; Muhammad Abrar Faiz; Yuxiang Hu; Qaisar Saddique (Water Resources Management, 2016)

Detrital mode and whole-rock geochemistry of the Miocene-Pliocene fluvial succession, Pishin Belt, Pakistan: implications on provenance and source area weathering in peripheral foreland basins - Aimal Khan Kasi; Akhtar Muhammad Kassi; Henrik Friis; Muhammad Umar; Mohibullah Mohibullah; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2016)

Reservoir attributes of a hydrocarbon-prone sandstone complex: case of the Pab Formation (Late Cretaceous) of Southwest Pakistan - Muhammad Umar; Abdul Salam Khan; Gilbert Kelling; Henrik Friis; Akhtar Muhammad Kassi (Arabian Journal of Geosciences, 2016)

Zinc-induced modulation of some biochemical parameters in a high- and a low-zinc-accumulating genotype of Cicer arietinum L. grown under Zn-deficient condition - Shadab Naseer Siddiqui; Shahid Umar; Muhammad Iqbal (Protoplasma, 2015)

Nitrate accumulation pattern in Brassica under nitrogen treatments - Samina Mazahar; Ovais Sareer; Shahid Umar; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Biosorption of heavy metals from aqueous solutions using indigenous and modified lignocellulosic materials - Muhammad Salman; Makshoof Athar; Umar Farooq (Reviews in Environmental Science and Bio/Technology, 2015)

RETRACTED ARTICLE: Impact of Drought Stress on Some Grain Quality Traits in Rice (Oryza sativa) - Zulqarnain Haider; Umar Farooq; Imad Naseem; Samta Zia; Muhammad Alamgeer (Agricultural Research, 2015)

A new rosane-type diterpenoid from Stachys parviflora and its density functional theory studies - Umar Farooq; Khurshid Ayub; Muhammad Ali Hashmi; Rizwana Sarwar; Afsar Khan; Mumtaz Ali; Manzoor Ahmad; Ajmal Khan (Natural Product Research, 2015)

Stratigraphic and sedimentological attributes in Hazara Basin Lesser Himalaya, North Pakistan: their role in deciphering minerals potential - Muhammad Umar; Muhammad Amjad Sabir; Muhammad Farooq; Malik Muhammad Saud Sajid Khan; Faridullah Faridullah; Umair Khan Jadoon; Abdul Salam Khan (Arabian Journal of Geosciences, 2015)

Recent Advancements in the Treatment of Municipal Wastewater Reverse Osmosis Concentrate—An Overview - Muhammad Umar; Felicity Roddick; Linhua Fan (Critical Reviews in Environmental Science and Technology, 2015)

Effect of alkaline pretreatment on delignification of wheat straw - Umar Asghar; Muhammad Irfan; Mehvish Iram; Zile Huma; Rubina Nelofer; Muhammad Nadeem; Quratulain Syed (Natural Product Research, 2015)

Assessment of groundwater vulnerability to anthropogenic pollution and seawater intrusion in a small tropical island using index-based methods - Nura Umar Kura; Mohammad Firuz Ramli; Shaharin Ibrahim; Wan Nor Azmin Sulaiman; Ahmad Zaharin Aris; Adamu Idris Tanko; Muhammad Amar Zaudi (Environmental Science and Pollution Research, 2015)

Assessment of cadmium accumulation, toxicity, and tolerance in Brassicaceae and Fabaceae plants—implications for phytoremediation - Naser A. Anjum; Shahid Umar; Muhammad Iqbal (Environmental Science and Pollution Research, 2014)

Molecular classification of Pakistani collared dove through DNA barcoding - Ali Raza Awan; Emma Umar; Muhammad Zia ul Haq; Sehrish Firyal (Molecular Biology Reports, 2013)

Synthesis, structure, anticancer, and antioxidant activity of para-xylyl linked bis-benzimidazolium salts and respective dinuclear Ag(I) N-heterocyclic carbene complexes (Part-II) - Rosenani A. Haque; Muhammad Adnan Iqbal; Patrick Asekunowo; A. M. S. Abdul Majid; Mohamed B. Khadeer Ahamed; Muhammad Ihtisham Umar; Sawsan S. Al-Rawi; Fouad Saleih R. Al-Suede (Medicinal Chemistry Research, 2013)

Genetic analysis of Newcastle disease virus from Punjab, Pakistan - Muhammad Zubair Shabbir; Muhammad Abbas; Tahir Yaqub; Nadia Mukhtar; Atta Subhani; Hasham Habib; Muhammad Umar Sohail; Muhammad Munir (Virus Genes, 2013)

Landslide dam and subsequent dam-break flood estimation using HEC-RAS model in Northern Pakistan - Mohsin Jamil Butt; Muhammad Umar; Raheel Qamar (Natural Hazards, 2013)

Novel quinolyl-thienyl chalcones and their 2-pyrazoline derivatives with diverse substitution pattern as antileishmanial agents against Leishmania major - Syed Umar Farooq Rizvi; Hamid Latif Siddiqui; Muhammad Nisar Ahmad; Matloob Ahmad; Mujahid Hussain Bukhari (Medicinal Chemistry Research, 2012)

Role of tissue plasminogen activator and plasminogen activator inhibitor polymorphism in myocardial infarction - Waqas Ahmed; Meera Malik; Imran Saeed; Amina Ali Khan; Ahmed Sadeque; Umar Kaleem; Nuzhat Ahmed; Muhammad Ajmal; Maleeha Azam; Raheel Qamar (Molecular Biology Reports, 2011)

Water quality fluctuations under floating net cages for fish culture in Lake Cirata and its impact on fish survival - Irzal EFFENDIE; Kukuh NIRMALA; Umar HASAN SAPUTRA; Agus Oman SUDRAJAT; Muhammad ZAIRIN; Hisashi KUROKURA (Fisheries Science, 2005)

A Preliminary Comparison of Plasma Fibrinogen Concentrations, Leukocyte Numbers and Erythrocyte Sedimentation Rate as Non-Specific Indicators of Inflammatory Conditions in Buffalo (Bubalis Bubalis) - M. Zargham Khan; G. Muhammad; A. Umar; S. Ali Khan (Veterinary Research Communications, 1997)